Regenerable VOC filtration media with improved selectivity and efficacy
By using the hydrophilic nuclear structure of porous water-stable metal-organic framework (MOF) material, the existing air filter media is solved inadequate saturation and selectivity in high humidity environments, and efficient capture of aldehyde compounds and media renewability are achieved.
Patent Information
- Application Number
- CN202080076613.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-04
- Filing Date
- 2020-11-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-11-04
AI Technical Summary
Existing air filter media are prone to saturation and lack selectivity in high humidity environments, and cannot effectively capture aldehyde volatile organic compounds, such as formaldehyde, and are difficult to regenerate without destroying their structural and chemical composition.
Porous water-stable metal-organic framework (MOF) materials are used to form hydrophilic nuclei in the MOF framework, and hydrogen bond interaction between alkaline groups and oxygen-containing substances is used to achieve selective adsorption of aldehydes, and the medium is renewable through thermal desorption or aqueous solution regeneration technology.
It realizes highly selective capture of aldehyde compounds in high humidity environments, avoids saturation, and reduces material consumption and operating costs through renewable technology.
Smart Images

Figure CN115003401B_ABST
Abstract
Description
Technical Field
[0001] The invention relates in particular to the use of porous crystalline solids consisting of metal-organic frameworks (MOFs) for the selective adsorption of aldehyde-type volatile organic compounds.
[0002] The MOF solid of the present invention can be used to improve the purification of dry or humid air, and to produce a regenerable filter medium for air purification, in particular a leak-free regenerable air filter medium.
[0003] References between square brackets [X] refer to the Reference List at the end of the Examples. Background Art
[0004] The air we breathe can be contaminated by pollutants, defined under Article L220-2 of the French Environmental Code as “chemical, biological or physical agents with harmful consequences that may endanger human health, harm biological resources and ecosystems, affect climate change, impair the properties of materials, cause excessive and offensive odours”.
[0005] Unlike outdoor air pollution, indoor air pollution was relatively unknown until the year 2000. Yet individuals spend 90 to 80% of their time in closed environments: homes, schools, workplaces or places designed to accommodate the public. The quality of the air we breathe can have effects on comfort and health, ranging from simple discomfort or irritation to more dangerous and deadly consequences, such as the development of allergies, asthma, lung cancer, poisoning, cardiovascular disease, chronic obstructive pulmonary disease, respiratory infections.
[0006] Air pollution is a major global health issue, as evidenced by the Sustainable Development Goals (SDOs) detailed in the 2030 Agenda and established by UN member states. These goals set targets to be achieved by 2030 and include the following three SDOs for air pollution: (i) reduce mortality from air pollution; (ii) ensure access to clean energy in housing; and (iii) ensure air quality in cities. In May 2018, the World Health Organization (WHO) published a critical assessment of air pollution: 7 million people die each year from exposure to ambient and household air pollution, or one in nine deaths worldwide is caused by air pollution-related diseases. Currently, more than 90% of the world's population lives in areas where air pollution exceeds WHO limits.
[0007] Ambient and household air pollution is one of the leading causes of premature mortality (all deaths before the age of 65) globally. Although often invisible and ignored as a risk, ambient and household air pollution has devastating consequences for the health of millions of people.
[0008] Air quality inside a residence differs from outdoor air quality in that pollutant concentrations are often much higher and chemicals are present that are not detectable outdoors. For example, a gas chromatography analysis dating back to 2007 identified nearly 20 VOCs in indoor air in 567 French residences, revealing that the main VOCs were aldehydes, and more specifically formaldehyde, which was found in the highest concentrations, followed by aromatic compounds: toluene and xylene.
[0009] Formaldehyde, also known as methanal, is a highly toxic and carcinogenic volatile organic compound (VOC). Although gaseous sources of formaldehyde emit less and less pollutants over time, it can take weeks, and sometimes even months or years for the vapors of this harmful substance to completely disappear. In addition, formaldehyde is emitted spontaneously during any combustion phenomenon (fire, tobacco smoke, vehicle emissions in garages / parking lots, etc.) and during human activities (cooking, wood stoves, burning of plant waste).
[0010] From a technological point of view, there are currently several technologies on the market that address the problem of indoor air pollution. The French company Air-Serenity uses a technology based on the use of air treatment filter cartridges designed to remove chemical compounds, particles and microorganisms in one go. More precisely, the technology uses HEPA F7 filter media to capture fine particles, adsorption sponges to capture volatile organic compounds (VOCs), and cold plasma for regeneration. Specifically, cold plasma is used to remove VOCs by reacting them with ozone and free radicals released by the plasma (to form CO at the end of the reaction chain). 2 and H 2 O) to regenerate the "sponge". The regeneration frequency is daily. This regeneration is not perfect and may wear out the sponge, and in any case the filter cartridge must be replaced at least once a year. To date, this technology is not available for general public use: at the end of its service life, it is sent back to the supplier for replacement by the consumer. In addition, several scientific studies have shown that plasma treatment rarely produces only CO 2 and water; more often, it produces free radicals that react incompletely and are potentially dangerous. Therefore, this technology is risky.
[0011] Beewair uses the DBD pyrolysis method (Dielectric Barrier Discharge to Generate Radicals) to pyrolyze harmful molecules (viruses, bacteria, VOCs, etc.) in the reactor and then reconstitute them into stable molecules present in the air (nitrogen, oxygen, water, etc.) through mineralization. The advantage is that there are no disposable filter cartridges; however, the technology is relatively expensive compared to purification systems based on filter media and lacks mineralization efficiency.
[0012] There are many companies such as Austin (an American company), Blueair, IQAir and major brands of home appliances whose filtration systems are based on HEPA filter media of activated carbon and zeolite coupled with fans to force the air through these filter media.
[0013] INOVAME has proposed a purification technology that allows the targeting of formaldehyde using a formulation of activated carbon and acetoacetamide [1, 2].
[0014] However, existing filter media have a number of important disadvantages. They are not very selective and tend to saturate quickly at high humidity levels, degrading performance over time. In addition, when the concentration of the absorbent is higher than the concentration of the pollutants in the filtered air, existing filter media tend to release pollutants concentrated within the filter media. They also must be replaced frequently and treated as sensitive materials at the end of their useful life, and must then be replaced with new filter media (thus consuming raw materials).
[0015] Existing adsorbent materials used in air filtration media lack leak-free capture capacity (i.e., they typically release formaldehyde under normal ambient conditions). They do not provide sufficient selectivity to ensure formaldehyde capture over other VOCs (capture of other VOCs can prevent formaldehyde capture). Finally, they do not allow for regeneration without destroying their structure and chemical composition (e.g., degradation and / or removal of grafted amines within the adsorbent structure).
[0016] To our knowledge, there are no renewable / recyclable air filtration media / purification media suitable for domestic VOC capture. Conventional filtration systems require return to the supplier for specific treatments: thermal treatment (by increasing the temperature to about 800°C) or chemical treatment (usually using solvents with high pH at low temperatures (about 100°C)). However, these methods have serious disadvantages because they result in material losses as well as significant energy costs.
[0017] Therefore, there remains a need to develop materials and air purification systems that selectively capture aldehydes, such as formaldehyde and / or acetaldehyde, and combine the following attractive properties:
[0018] - Filtration selectivity and high adsorption capacity (to avoid accelerated saturation phenomena)
[0019] - Adsorption stability under representative environmental conditions (to avoid release / leakage phenomena)
[0020] - Recyclability of the filter media according to protocols suitable for domestic and professional use (to avoid expensive consumables that often lead to poor performance of the air purification media). BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1: List of exemplary MOFs tested for selective aldehyde adsorption in the context of the present invention, along with their properties and physicochemical characteristics.
[0022] Figure 2 : shows the PXRD pattern of Al-3,5-PDA prepared in Example 1.1 at room temperature.
[0023] Figure 3 : shows the nitrogen adsorption isotherm of Al-3,5-PDA prepared in Example 1.1 at 77 K, which indicates a type I isotherm and shows a nitrogen adsorption isotherm with a molecular weight of about 1343 m 2 / g specific surface area (BET) and 0,49cm 3 / g of pore volume of microporous material.
[0024] Figure 4 : shows the TGA curve of Al-3,5-PDA prepared in Example 1.1, showing the dehydration from 25°C to 100°C and the degradation of Al-3,5-PDA from 350°C. Thermogravimetric analysis (at O 2 The first weight loss from 25°C to 100°C corresponds to the loss of water trapped in the micropores; the second weight loss shows that the material starts to degrade from 350°C and is completely degraded at 500°C.
[0025] Figure 5 : shows the FT-IR spectrum of Al-3,5-PDA prepared in Example 1.1 (the upper part of the spectrum is cut off; this corresponds to the saturation of the MCT detector (mercury cadmium telluride)). FT-IR analysis shows the presence of carboxylate groups bonded to aluminum (at 1680 and 1335 cm -1 between the figure); hydroxyl group (-OH) (3692cm -1 ); -NH group (3330cm -1 ); =CH group (3160cm -1 ).
[0026] Figure 6 : shows nitrogen adsorption and desorption of the shaped MOF prepared in Example 3 with polyvinyl acetate as binder at 77 K.
[0027] Figure 7 : shows nitrogen adsorption and desorption of the shaped MOF prepared in Example 3 with a polyvinyl butyral binder at 77 K.
[0028] Figure 8 : A schematic diagram of the operating system used in the embodiment is shown.
[0029] Fig. 9 : A schematic diagram showing the operating unit used in the embodiment.
[0030] Figure 10: shows the temperature at 23°C at 20% O 2 , 90% RH and 415 ppm formaldehyde composition at a flow rate of 20 cc / min at 23°C performed in Example 5 (the ordinate is the maximum formaldehyde adsorption capacity (mmol / g), and the abscissa is the maximum water adsorption capacity (mmol / g)).
[0031] Fig.11 : FT-IR spectra obtained during the adsorption of formaldehyde dosages on Al-3,5-PDA are shown (the upper part of the spectrum is cut off; this corresponds to the saturation of the MCT detector (mercury cadmium telluride)). Each spectrum corresponds to the adsorption molar amount of formaldehyde, including from bottom to top: 0.001mmol / g, 0.020mmol / g, 0.03mmol / g, 0.04mmol / g, 0.058mmol / g, 0.075mmol / g, 0.093mmol / g, 0.110mmol / g, 0.132mmol / g, 0.153mmol / g, 0,174mmol / g, 0.196mmol / g, 0.217mmol / g, 0.252mmol / g, 0.287mmol / g, 0.322mmol / g, 0.357mmol / g, 0.391mmol / g, 0.425mmol / g, 0.4 The weight of the samples was 0.59mmol / g, 0.492mmol / g, 0.526mmol / g, 0.558mmol / g, 0.604mmol / g, 0.649mmol / g, 0.693mmol / g, 0.737mmol / g, 0.780mmol / g, 0.824mmol / g, 0.867mmol / g, 0.909mmol / g, 0.951mmol / g, 0.993mmol / g, 1.04mmol / g, 1.09mmol / g, 1.13mmol / g, 1.19mmol / g, 1.233mmol / g, 1.28mmol / g, 1.32mmol / g, and 1.37mmol / g. (all normalized to the mass of the Al-3,5-PDA pellets).
[0032] Figure 12: shows background-subtracted FT-IR spectra obtained during adsorption of formaldehyde on Al-3.5-PDA. a) At 3675 to 3460 cm -1 b) 3292 to 1700 cm -1 , c) 1320 to 1200 cm -1 , d) 1150 to 1064 cm -1, e) 3773 to 2730 cm -1 .
[0033] Fig.13 : Inorganic infinite chain of formaldehyde; pyrazole linker and framework μ 2 Reaction scheme between the -OH hydroxyl group and the remaining nitrogen from the pyrazole linker. For clarity, only one pyrazole linker and hydroxyl group are shown schematically.
[0034] Fig.14 : shows background-subtracted FT-IR spectra obtained during the adsorption of formaldehyde on DUT-67(Zr)-PZDC a) between 3675 and 1700 cm -1 b) 1350 to 1180 cm -1 , c) 1160 to 1020 cm -1 .
[0035] Fig.15 : Shown in D 2 Regeneration in aqueous solution after CO (labeled formaldehyde) adsorption (Al-3.5-PDA): 1) at 4000-500 cm -1 FT-IR spectrum in the spectral range. 2) In the range of 2300-2050cm -1 FT-IR spectra within the spectral range, 3) D present in the sample 2 a) FT-IR spectrum of Al-3.5-PDA after heat treatment. b) FT-IR spectrum of Al-3.5-PDA after heat treatment. 2 IR spectrum obtained after saturation with CO, c) FT-IR spectrum obtained after rinsing the sample with 100 mL of water. d) FT-IR spectrum obtained after cumulative rinsing of the sample with 100 mL of water. e) FT-IR spectrum obtained after quenching the sample in 100 mL of water for 3 h. f) FT-IR spectrum obtained after quenching the sample in 100 mL of water for 3 h. All steps are cumulative and performed at room temperature (23 °C). 3) Percentage of formaldehyde remaining in the sample after each treatment relative to the initial concentration after saturation. After treatments in e) and f), the sample is completely free of formaldehyde.
[0036] Fig.16 : shows the regeneration in EtOH solution after toluene adsorption (Al-3.5-PDA): 1) at 4000-500 cm -1 FT-IR spectrum in the spectral range. 2) The spectral range is 3100-2850cm -1FT-IR spectrum of the sample. 3) % of toluene present in the sample. a) FT-IR spectrum obtained after saturation with toluene (equilibrium pressure of 8 mbar). b) FT-IR spectrum obtained after rinsing the sample with a few drops of EtOH. c) FT-IR spectrum obtained after rinsing the sample with 100 mL of EtOH. d) FT-IR spectrum obtained after quenching the sample in 100 mL of EtOH for 3 hours. All steps are cumulative and performed at room temperature (23°C). 3) The percentage of toluene remaining in the sample after each treatment relative to the initial concentration after saturation. After treatment d), the sample is completely free of toluene.
[0037] Fig.17 : shows the regeneration in aqueous solution after toluene adsorption (Al-3.5-PDA): 1) at 4000-500 cm -1 FT-IR spectrum in the spectral range. 2) The spectral range is 3100-2800cm -1 FT-IR spectrum of the sample. 3) % of toluene present in the sample. a) IR spectrum of Al-3.5-PDA obtained after thermal activation at 200°C for 1 hour b) FT-IR spectrum obtained after saturation with toluene at an equilibrium pressure of 8 mbar. c) FT-IR spectrum obtained after quenching the sample in 100 mL of water for 3 h. All steps are cumulative and performed at room temperature (23°C).
[0038] Fig.18 :It shows that the thermally activated UiO-66-NH 2 FT-IR spectra recorded at 100 °C and 200 °C. From top to bottom, FTIR spectra were recorded at room temperature, 100 °C and 200 °C.
[0039] Fig.19 :UiO-66(Zr)-NH 2 Adsorption of formaldehyde on the sample. a) At 3800-1600 cm -1 In the spectral region of UiO-66(Zr)-NH 2 Direct FT-IR spectrum recorded when formaldehyde was adsorbed on the surface; b) at 3800-1600 cm -1 In the spectral region of UiO-66(Zr)-NH 2 Background-subtracted FT-IR spectrum recorded when formaldehyde was adsorbed on the surface of UiO-66(Zr)-NH 2 At 3800-1600cm -1 Direct FT-IR spectra recorded upon thermal regeneration in the spectral region of .
[0040] Fig. 20 : shows a) at 3750-1652cm -1 In the spectral region of UiO-66(Zr)-NH2 Background subtracted FT-IR spectrum recorded during thermal regeneration of the sample. b) 1203-869 cm -1 In the spectral region of UiO-66(Zr)-NH 2 Background subtracted FT-IR spectra recorded upon thermal regeneration of the sample. c) [from top to bottom], incremental subtraction between background subtracted FT-IR spectra (dashed FT-IR spectrum: poly(formaldehyde)).
[0041] Fig.21 : Shown in MIL-125(Ti)-NH 2 Adsorption of formaldehyde. a) At 3800-1600cm -1 In the spectral region of MIL-125(Ti)-NH 2 Background-subtracted FT-IR spectrum recorded when formaldehyde was adsorbed on the surface of the substrate; b) at 1200-850 cm -1 In the spectral region of MIL-125(Ti)-NH 2 Background-subtracted FTIR spectra recorded upon adsorption of formaldehyde.
[0042] Fig. 22 : shows the thermal desorption of HCHO in humid air (in %). 2 The experiment was conducted at a flow rate of 20 mL / min of a (90% RH) composition.
[0043] Fig.23 : shows a) FT-IR spectra during thermal regeneration, from top to bottom, saturated: saturated with formaldehyde at an equilibrium pressure of 0.1 mbar, 80°C: FT-IR spectrum acquired after a plateau period (48 h) at 80°C, 110°C: cumulative FT-IR spectrum acquired after a plateau period (2 h) at 110°C, reference: reference spectrum acquired before adsorption of formaldehyde b) during thermal regeneration at 3780-2280 cm -1 Background-subtracted FT-IR spectra in the spectral region.
[0044] Fig.24 : Shown at 1700-1000cm -1 In the spectral region of imidazole / Al 2 O 3 Background-subtracted FT-IR spectrum obtained when formaldehyde is adsorbed on a mixture of 1:10 (mass ratio 1).
[0045] Figure 25: shows the dynamic flow rate of CO at 20 mL / min 2 Breakthrough curves of co-adsorption of 2-nitropropene (3000 ppm) and water (RH50%).
[0046] Fig.26: shows the maximum CO obtained in Example 7 under the following experimental conditions 2 (mmol / g) adsorption capacity.
[0047] Fig. 27 : shows a) the use of CO on a flat Al-3.5-PDA 2 FT-IR spectra acquired during formaldehyde adsorption, from bottom to top: stepwise increase of chemisorbed formaldehyde b) on saturated Al-3.5-PDA with CO 2 FTIR spectrum acquired when formaldehyde is adsorbed, from top to bottom: at 2355-2320 cm -1 The spectral region of chemically adsorbed formaldehyde increases (physical adsorbed CO 2 Reduction) d) (bottom) on saturated Al-3.5-PDA with CO 2 FTIR spectra acquired during formaldehyde adsorption; (top) CO adsorption with formaldehyde on saturated Al-3.5-PDA 2 (top blue spectrum), followed by evacuation (top red spectrum) e) with CO 2 Formaldehyde adsorption on saturated Al-3.5-PDA (green spectrum from top to bottom), followed by CO adsorption on Al-3.5-PDA saturated with formaldehyde 2 (top blue spectrum) and subsequently evacuated under dynamic vacuum (top red spectrum). -1 c) The previous figures d) and e) investigate the complete FTIR range.
[0048] Fig.28 : Shows coverage and absolute value of desorption rate as a function of temperature. Obtained during linear heating of Al-3.5-PDA saturated with deuterated formaldehyde at a heating rate of 3°C / min. For clarity, data are expressed in %.
[0049] Fig.29 : Show Curve function used in Example 7j).
[0050] definition
[0051] To facilitate understanding of the present invention, a number of terms and phrases are defined below:
[0052] As used herein, except in the claims, the terms "a," "an," "the," and / or "said" mean one or more. As used herein in the claims, when used in conjunction with the words "comprise," "comprises," and / or "comprising," the terms "a," "an," "the," and / or "said" may mean one or more. As used herein and in the claims, the terms "having / has / have," "is," "including," "includes," and / or "include" have the same meaning as "comprising / comprises / comprise." As used herein and in the claims, "another" may mean at least a second or more.
[0053] The phrases "combinations thereof," "mixtures thereof," etc., following a list, use of "and / or" as part of a list, a list within a table, use of "etc." as part of a list, the phrase "such as," and / or a list with "for example" or "i.e." within square brackets refer to any combination (e.g., any subset) of a group of listed components, and combinations and / or mixtures of related species and / or embodiments described herein that are not directly placed in such a list are also contemplated. Such related and / or similar genera, subgenera, species, and / or embodiments described herein are considered to be in the form of individual components that may be claimed, as well as mixtures and / or combinations described in the claims as "at least one selected from...", "mixtures thereof," and / or "combinations thereof"
[0054] In general, the term "substituted", whether or not it is followed by the term "optionally", and the substituents contained in the chemical formulas of the present invention, refers to the replacement of hydrogen radicals in a given structure with specified substituent radicals. When more than one position in any given structure can be substituted by more than one substituent selected from a particular group, the substituents may be the same or different at each position. As used herein, the term "substituted" is intended to include all permissible substituents of organic compounds.
[0055] The term "alkyl" as used herein refers to straight and branched C1-C10 alkyl groups. Similar conventions apply to other general terms such as "alkenyl", "alkynyl", etc. "Low carbon number alkyl" as used herein is used to represent those alkyl groups (substituted, unsubstituted, branched or unbranched) with about 1-6 carbon atoms. Illustrative alkyl groups include, but are not limited to, for example, methyl, ethyl, n-propyl, isopropyl, allyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, sec-pentyl, isopentyl, tert-pentyl, n-hexyl, sec-hexyl, part, etc., in addition, it can carry one or more substituents. Alkenyl groups include, but are not limited to, for example, vinyl, propenyl, butenyl, 1-methyl-2-butene-1-yl, etc. Representative alkynyl groups include, but are not limited to, ethynyl, 2-propynyl (propargyl), 1-propynyl, etc.
[0056] As used herein, the term "heteroaliphatic" refers to an aliphatic moiety in which one or more carbon atoms in the backbone have been replaced by heteroatoms. Thus, a heteroaliphatic group refers to an aliphatic chain containing one or more oxygen, sulfur, nitrogen, phosphorus or silicon atoms, i.e., substituted carbon atoms. The heteroaliphatic moiety may be branched or straight chain unbranched. Similar conventions apply to other general terms such as "heteroalkyl", "heteroalkenyl", "heteroalkynyl", etc.
[0057] As used herein, the term "heterocyclic" or "heterocycle" refers to the nature of combining heteroaliphatic and cyclic compounds, and includes, but is not limited to, saturated and unsaturated monocyclic or polycyclic heterocycles, such as compounds of morpholinyl, pyrrolidinyl, furanyl, thiopyranyl, pyrrolyl, etc., which are optionally substituted with one or more functional groups as defined herein. In certain embodiments, the term "heterocycle" refers to a non-aromatic 5-, 6-, or 7-membered ring or polycyclic group, including, but not limited to, a bicyclic or tricyclic group containing a fused six-membered ring with one to three heteroatoms independently selected from oxygen, sulfur, and nitrogen, wherein (i) each 5-membered ring has 0 to 2 double bonds and each 6-membered ring has 0 to 2 double bonds, (ii) nitrogen and sulfur heteroatoms can be optionally oxidized, (iii) nitrogen heteroatoms can be optionally quaternized, and (iv) any of the above heterocycles can be fused with an aryl ring or a heteroaryl ring. Representative heterocycles include, but are not limited to, pyrrolidinyl, pyrazolinyl, pyrazolidinyl, imidazolinyl, imidazolidinyl, piperidinyl, piperazinyl, oxazolidinyl, isoxazolidinyl, morpholinyl, thiazolidinyl, isothiazolidinyl, and tetrahydrofuranyl.
[0058] In general, the term "aromatic" or "aryl" as used herein refers to a stable, substituted or unsubstituted, unsaturated, monocyclic or polycyclic hydrocarbon moiety, preferably having 3 to 14 carbon atoms, containing at least one ring that satisfies Hückle's rule for aromaticity. Examples of aromatic moieties include, but are not limited to, phenyl, indanyl, indenyl, naphthyl, phenanthrenyl, and anthracenyl.
[0059] As used herein, the term "independently" refers to the fact that the substituents, atoms or moieties to which these terms refer are independently selected from the list of variables (ie, they may be identical or the same) from one another.
[0060] As used herein, "about" refers to any inherent measurement error or rounding of a value (e.g., a measured value, a calculated value such as a ratio), and therefore the term "about" can be used with any value and / or range. As used herein, the term "about" can refer to a change of ±5% of a specified value. For example, in some embodiments, "about 50"% can have a change of 45% to 55%. For integer ranges, the term "about" may include one or two integers greater than and / or less than the integer. Unless otherwise specified herein, the term "about" is intended to include values close to the range, such as weight %, temperature, which are equivalent in terms of the functionality of the relevant individual components, compositions or embodiments.
[0061] As used herein, the term "and / or" means any one, any combination of items, or all of the items associated with the term.
[0062] As will be understood by the skilled artisan, all numbers, including those expressing amounts of ingredients, properties such as molecular weight, reaction conditions, etc., are approximate and are understood to be optionally modified in all instances by the term "about". These values may vary depending on the desired properties sought to be obtained by one skilled in the art utilizing the teachings described herein. It is also understood that the values inherently contain variability necessarily resulting from the standard deviation found in their corresponding test measurements.
[0063] As will be understood by those skilled in the art, for any and all purposes, particularly with respect to providing a written description, all ranges described herein also include any and all possible subranges and combinations of their subranges, as well as individual values, particularly integer values, constituting the range. The range (e.g., weight percent or carbon group) includes each specific value, integer, decimal, or identity within the range. Any listed range can be easily identified as fully describing and capable of decomposing the same range into at least equal half, one-third, one-quarter, one-fifth, or one-tenth. As a non-limiting example, each range discussed herein can be easily decomposed into a lower third, a middle third, and an upper third, etc.
[0064] As will also be understood by those skilled in the art, all language such as "at most," "at least," "greater than," "less than," "exceeds," "or more" and the like includes the recited numbers, and these terms refer to ranges that can then be subdivided into sub-ranges as discussed above. In the same manner, all ratios described herein also include all sub-ratios that fall within the broader ratio. Thus, the specific values recited for radicals, substituents, and ranges are for illustration only; they do not exclude other defined values or other values within defined ranges for radicals and substituents.
[0065] Those skilled in the art will also readily recognize that where members are grouped together in a common manner, such as in a Markush group, the present invention encompasses not only the entire group listed as a whole, but also each individual member of the group and all possible subgroups of the main group. In addition, for all purposes, the present invention encompasses not only the main group, but also the main group without one or more group members. Thus, the present invention contemplates the explicit exclusion of any one or more members of the described group. Thus, the proviso may apply to any disclosed class or embodiment, thereby excluding any one or more of the described elements, species, or embodiments from the class or embodiment, such as used in an explicit negative limitation.
[0066] As used herein, the term "solid" refers to any type of crystalline material. The solid may be, for example, in the form of crystals, powders or particles in various forms, such as spherical, lamellar, etc. The particles may be in the form of nanoparticles.
[0067] As used herein, "humid environment" means an atmospheric environment containing water vapor. It can be air with water vapor. The amount of water vapor present in an environment such as air increases with increasing temperature. The difference in the content of water vapor in a group of air may be quite large. For example, a group of air close to saturation may contain 28 grams of water per cubic meter of air at 30°C, but only 8 grams of water per cubic meter of air at 8°C. Water vapor (Water vapor) or steam or water vapor (aqueous vapor) is the gas phase of water. It is a state of water in the hydrosphere. Under typical atmospheric conditions, water vapor is continuously produced by evaporation and removed by condensation. The vapor content in the air can be measured with a device called a hygrometer. In the present invention, the amount of water vapor in the environment such as air can be from higher than dry air to saturation, such as from 10°C to 30°C, such as at room temperature, i.e. at a temperature between 18°C and 28°C. As used herein, the term "higher than normal humid environment" refers to the humidity level of the environment as defined above, which is higher than the conventional acceptance threshold of the normal humid environment for human comfort. This "normal humidity" threshold is typically about 25%-30% relative humidity (see Ashrae Fundamentals Handbook, SI Edition, 2001, p. 24.5. [3]). In the context of the present invention, an above normal humid environment refers to >60% relative humidity, still preferably ≥70% relative humidity, still preferably ≥80% relative humidity, up to 100% relative humidity. Indoor environments such as museums, galleries, libraries and archives are typically associated with normal relative humidity levels above about 40% RH.
[0068] MOFs are composed of bridging organic ligands, also known as "linkers" or "spacers", which remain intact throughout the synthesis process and act as linkers in the network of the resulting MOF structure. As used herein, the term "ligand" or "linker" or "spacer" refers to a ligand that coordinates to at least two metals, participates in providing distance between these metals and participates in forming voids or pores, also known as "cores" in MOFs.
[0069] As used herein, the term "average pore size" will be understood to refer to the MOF pore size (or pore diameters) as conventionally used in the art, such as measured by the nitrogen adsorption / desorption isotherm method at -196 °C over a period of 10 5 Calculated in Pa (1 bar).
[0070] As used herein, the term "water-stable MOF" refers to those MOFs that do not exhibit structural damage when exposed to water. MOF water stability can be evaluated by determining whether the MOF structure remains stable in a water stability test. This is typically done by comparing typical chemical signatures between the exposed sample and the original sample. Chemical signatures can be powder X-ray diffraction (PXRD) patterns and BET surface area based on gas adsorption capacity, which can be a good indicator of whether the MOF will lose its crystallinity or structural porosity after exposure to water content. In general, MOF structures are susceptible to attack by water molecules, which can result in ligand displacement, phase changes, and / or structural decomposition. Water-stable MOF structures are strong enough to prevent water molecules from invading the MOF framework, resulting in a loss of crystallinity and overall porosity. See Wang et al. 2016
[31] . Thus, a MOF is water-stable when the MOF crystal structure (as measured by X-ray diffraction pattern or IR spectroscopy) and average pore size (as calculated by nitrogen adsorption / desorption isotherm method at -196°C under 105 Pa (1 bar)) remain unchanged within experimental error after exposure to a gas environment with 50% relative humidity (RH) at 100°C and atmospheric pressure for 24 hours, or after treatment in water at 100°C for 12 hours.
[0071] As used herein, the expressions "hydrophilic MOF" or "MOF with a hydrophilic core" and conversely "hydrophobic MOF" or "MOF with a hydrophobic core" do not deviate from the conventional meaning of these terms in the field of MOFs.
[0072] The hydrophilic / hydrophobic properties of a MOF are directly related to the organic ligands of the MOF. A hydrophilic MOF will present hydrophilic ligands that are attracted to water molecules; typically, ligands with polar groups that allow hydrogen bonding with water or polar solvents (e.g., -NH 2 ;-OH;-NO 2 In contrast, a hydrophobic MOF will present organic ligands that are not attracted to water (e.g., -CH 3 ). Steric hindrance around the metal sites of the MOF that can interact with water can also increase the hydrophobicity of the material. This may involve the use of ligands functionalized with alkyl groups or densification of the inorganic part. Vapor phase water sorption experiments allow distinguishing MOFs with hydrophilic or hydrophobic properties. Hydrophilic materials will present type I isotherms (microporous materials) with substantial adsorption at low partial pressures. Quite hydrophobic materials will present type V isotherms with substantial adsorption for intermediate partial pressures (0.2 < P / P) due to capillary condensation in the pores. 0 <0.6) has significant adsorption. In the extreme case of superhydrophobic materials, no matter what the partial pressure is, water is completely not adsorbed. See reference
[32]
[0073] As used herein, the term "regenerable" when used to define the air filter medium / purification medium according to the present invention means that the filter medium / purification medium retains >0%, preferably ≥25%, more preferably ≥50%, even more preferably ≥75%, most preferably ≥99% of its adsorption / filtration capacity after reaching saturation and undergoing a regeneration process as described herein, after at least one regeneration cycle, preferably after 2, 3, 4, 5, 7, 8, 9 regeneration cycles, more preferably after 10 or more regeneration cycles. The filter medium can be thermally regenerable and / or regenerable by washing with water and / or an aqueous alcoholic solution. The filter medium can be regenerated durably and with low energy consumption by low-temperature thermal desorption and / or by washing in water or an aqueous alcoholic solution.
[0074] The filter medium may be thermally regenerable. Thus, the filter medium may be regenerated permanently and with low energy consumption to ≥75%, preferably 90%, of its adsorption / filtration capacity by heating the filter medium to a temperature of ≥70°C, preferably 75°C to 250°C, more preferably below 100°C, and then subjecting the filter medium to low-temperature thermal desorption. Thermal regeneration of the filter medium may be carried out under an inert gas or a primary vacuum (e.g. about 10 -2 Ba) is performed.
[0075] The filter medium can be regenerated by washing with water and / or a hydroalcoholic solution. Thus, by cleaning with water and / or a hydroalcoholic solution at room temperature, the filter medium can be regenerated durably and with low energy consumption. Preferably, by washing with water and / or a hydroalcoholic solution at room temperature, the filter medium can be regenerated to ≥ 75%, preferably 90%, of its adsorption / filtration capacity after at least one regeneration cycle. DETAILED DESCRIPTION
[0076] As described above, there is a pressing need to develop materials and air purification systems that selectively and efficiently capture aldehydes, such as formaldehyde, from the air in the presence of other VOC pollutants, that are leak-free and easily recyclable / regenerable by users in both home and professional settings alike.
[0077] Herein, provided is a use of a porous water-stable metal-organic framework (MOF) material for selectively adsorbing aldehyde volatile organic compounds such as formaldehyde and / or acetaldehyde from a gas environment such as air, wherein the gas environment may contain other pollutants in addition to the aldehyde volatile organic compounds, wherein the water-stable MOF material comprises < Preferred The invention relates to a method for selectively adsorbing aldehyde volatile organic compounds such as formaldehyde and / or acetaldehyde from a gas environment such as air, which may contain other pollutants in addition to aldehyde volatile organic compounds, and a hydrophilic core formed by basic groups and oxygen-containing species that accept or donate hydrogen bonds in the MOF framework, wherein the basic groups are covalently bonded to the MOF framework. Therefore, a method for selectively adsorbing aldehyde volatile organic compounds such as formaldehyde and / or acetaldehyde from a gas environment such as air is provided, wherein the gas environment may contain other pollutants in addition to aldehyde volatile organic compounds, and the method comprises contacting the gas environment such as air with a water-stable MOF material, wherein the water-stable MOF material comprises < Preferred and a hydrophilic core formed by basic groups and oxygen-containing species that accept or donate hydrogen bonds in the MOF framework, wherein the basic groups are covalently bonded to the MOF framework.
[0078] In another aspect, there is provided a use of a porous water-stable metal-organic framework (MOF) material alone or mixed with other porous materials such as other MOFs, zeolites and / or activated carbon for improving the purification of dry or humid air, wherein the water-stable MOF material comprises < Preferred The invention relates to a method for purifying dry or humid air, wherein the method comprises contacting the air to be purified with a water-stable MOF material, wherein the water-stable MOF material comprises: Preferred The method comprises a hydrophilic core formed by a basic group and an oxygen-containing species that accepts or donates hydrogen bonds in the MOF framework, wherein the basic group is covalently bonded to the MOF framework. The method can be carried out at a temperature range of 10°C to 50°C, and is generally carried out at ambient temperature.
[0079] In yet another aspect, the present invention provides a use of a porous water-stable metal-organic framework (MOF) material for manufacturing a regenerable filter medium for air purification, wherein the porous water-stable metal-organic framework material comprises < For example The invention relates to a method for preparing a regenerable filter medium for air purification, wherein the method comprises coating a suitable carrier with a water-stable MOF material, wherein the water-stable MOF material comprises: For example and a hydrophilic core formed by basic groups and oxygen-containing species that accept or donate hydrogen bonds in the MOF framework, wherein the basic groups are covalently bonded to the MOF framework.
[0080] In the above aspects and throughout this document, the gaseous environment (e.g., air) can be dry or humid (i.e., relative humidity in the range of 0% to 100%). For example, it can be air with a relative humidity of 15% to 95%. The gaseous environment can, for example, be air with a normal humidity level that is comfortable for humans (approximately 25%-30% relative humidity). The gaseous environment can, for example, be air with a humidity level that is higher than the normal humidity level that is comfortable for humans ("above normal humidity environment"). Therefore, in the above aspects and throughout this document, the gaseous environment can be air with a relative humidity of >30%, such as ≥35% relative humidity, such as ≥40% relative humidity, up to 100% relative humidity.
[0081] In each of the above aspects and throughout this document, a water-stable MOF material may have ≥ (For example ≥ ) to accommodate the kinetic diameter of formaldehyde. Thus, the average pore size (D) of the water-stable MOFs useful in the context of the present invention can be Preferably, it can be
[0082] The pore size distribution of MOF can be calculated according to the adsorption isotherm of some gases (such as nitrogen). The distribution does not give a single value of the pore size, but gives a volume distribution associated with each pore size (pore diameter or pore width, depending on the geometry of the pore). Therefore, the nitrogen adsorption / desorption isotherm method (-196°C) is intended to cover various possible pore geometries (e.g., tetrahedron, octahedron) of MOF materials. MOFs generally have precise pore sizes, and the distribution is generally narrow. Therefore, the nitrogen adsorption / desorption isotherm method (-196°C) is particularly suitable for the determination of the average pore size of MOF materials. The method for measuring the average pore size of MOF is well documented in the literature. There are several methods to perform this type of calculation, and for example, IUPAC gives some suggestions (see Thommes et al., IUPAC Technical Report, Pure Appl. Chem., 2015, 87 (9-10), 1051-1069).
[24] See also Rouquerol, F.; Rouquerol, J.; Sing, K. Adsorption by powders and porous solids; Academic Press: San Diego, 1999, for a more extensive discussion of this topic. [4]
[0083] Alternatively, the maximum and limiting pore sizes can be estimated from crystallographic data by simulating gas molecules filling the pores (L. Skrisov and A. Harrison, Mol. Simul., 2011, 37, 1248-1257 [5]), which allows the calculation of the average pore size. In short, the crystal structure of the MOF can be determined from the diffraction pattern (X-ray patterns are the most common). Several computational methods are currently proposed in the literature to estimate the pore size (cages and windows) and surface area from a well-defined crystal structure. These computational methods are essentially based on simulating the adsorption of probe molecules on the pore surface. Reference [5] describes a method and reports a computer program to determine the most likely pore size, and therefore the average pore size of the MOF.
[0084] Regardless of the method used, if applied properly, they will agree within experimental error. However, in the context of the present invention, all values of average pore size of MOFs mentioned in this document are based on the average pore size of MOFs at 10 5 Nitrogen adsorption / desorption isotherm method at Pa (1 bar) (at -196°C).
[0085] In the above aspects, the use / method can be carried out at a conventional temperature range used in the field of air filtration / purification systems, for example, between 10°C and 50°C.
[0086] Advantageously, the water-stable metal-organic framework (MOF) material can be used alone or can be mechanically mixed with other porous materials (other MOFs different from the water-stable MOF material, zeolites, carbon).
[0087] In each of the above aspects and throughout this document, the fact that "the basic groups are covalently bonded to the MOF framework" means that these basic functional groups are not bonded to the metal sites of the MOF. Instead, the basic groups / functional groups are covalently bonded to the ligands that constitute the MOF framework. Therefore, the basic groups / functional groups present in the MOF framework are therefore more sustainable for capturing aldehydes and are stable upon thermal and / or solvent regeneration. In fact, in the case of basic groups / functional groups bonded to the metal sites of the MOF, there is a risk that they will be removed during water and / or thermal regeneration processes.
[0088] Advantageously, in each of the above aspects, the regenerable filter media can be leak-free with respect to aldehyde volatile organic compounds. In addition to selectively adsorbing aldehydes in the presence of other VOCs and / or in humid air, the MOFs useful in the context of the present invention also have the ability to retain aldehydes such as formaldehyde and / or acetaldehyde from the polluted air the first time it passes through the filter media with maximum efficiency, without releasing aldehydes even when the filter media is saturated and / or even when the temperature is elevated (typical operating temperatures envisioned are in the range of 10°C-50°C).
[0089] As used herein, when referring to the regenerable filter media of the present invention, the term "no leakage" refers to the ability of the filter media to retain 100% of the adsorbed aldehydes at atmospheric pressure (1 atm, 101325 Pa) and at operating temperatures in the range of 10°C-50°C. -1 The latter also applies when the air velocity flows through the filter medium at an air velocity of 100%. For example, in the case of formaldehyde, the leak-free adsorption capacity of the adsorbent corresponds to the amount of formaldehyde adsorbed by the adsorbent in the case of 100% filtration action in the formaldehyde (no formaldehyde molecules are detected at the outlet of the filter unit containing the adsorbent material). In other words, the "leak-free adsorption capacity" of the adsorbent material corresponds to the absence of a risk of releasing aldehydes over time. Depending on the environmental conditions (temperature, humidity, aldehyde concentration in the air), conventional adsorbents such as activated carbon can release the stored pollutants. In contrast, the MOF adsorbents according to the invention, such as Al-3,5-PDA, will release the stored pollutants under normal environmental conditions. Won't This is done until the no-leak storage capacity is exceeded.The no-leak adsorption capacity of the adsorbent can be determined using an operating unit in combination with mass spectroscopy and IR spectroscopy, such as described in the Examples section.
[0090] Box Atom
[0091] The MOF metal may be selected from any metal that promotes water stability and is capable of producing a MOF whose basic part is not bonded to the metal. Advantageously, the MOF metal may be selected from a trivalent or tetravalent metal from the rare earth metals (Sc, Y, Tb, Gd, Ce, Ln, La), Ti, Zr, Fe, Al or Cr; preferably Sc, Y, Ln, La, Ti, Zr, Fe, Al or Cr; preferably Ti, Zr, Fe, Al or Cr; more preferably Fe, Al, Ti or Zr, most preferably Al or Zr.
[0092] Ligand
[0093] In general, the ligands of the water-stable MOF framework can be selected from dicarboxylic acid, tricarboxylic acid or tetracarboxylic acid ligands; dicarboxylic acid ligands are preferred. The ligands can have a basic group covalently attached thereto (e.g., -NH 2 The basic group may be covalently bonded to the ligand, but there is no bond between the basic group and the MOF metal site. The basic group may be preferably embedded in the ligand, but there is no bond between the basic group and the MOF metal site. The basic group may be, for example, in the form of a formate, carboxylate, -NH 2 or in the form of -NH- groups, preferably -NH 2or -NH- groups. Thus, the ligands of the water-stable MOF framework may also be selected from N-heterocyclic ligands, but without a bond between the basic group and the MOF metal site. When the N atom constituting the N-heterocyclic ring of the ligand is involved in the bond to the MOF metal site, the N-heterocyclic ligand may carry at least one additional basic group (e.g., formate, carboxylate, -NH-) that is not involved in the bond to the MOF metal site. 2 or -NH- group, preferably -NH 2 or -NH- group, most preferably -NH 2 Group), such as an amino-imidazole salt ligand.
[0094] Ligand Best Practice
[0095] The best mode of practicing the invention involves MOFs with ligands having basic groups embedded within the ligands (e.g., -NH- groups contained in the pyrazolyl core) without bonding between the basic groups and the MOF metal sites. This excludes the less preferred variants described in this disclosure, in which the basic groups can be formate, carboxylate, or -NH 2 The group is preferably covalently grafted to the MOF ligand (i.e., an aliphatic, heterocyclic or aromatic ligand to which at least one formate, carboxylate or -NH 2 Group, preferably NH 2 -NH on the substituent of the group 2 Therefore, the best approach excludes amino-aromatic metal carboxylate MOFs (i.e., MOFs with NH 2 MOF materials with aromatic ligands of the group), such as UiO-66(Zr)-NH 2 / MIL-125(Ti)-NH 2 / MIL-101(Cr)-ED; and amino-heterocyclic metal carboxylate MOFs (i.e., having NH 2The MOF material of heterocyclic ligand of the group is preferably a MOF constructed with amino-imidazole salt ligand (for example, 2-aminoimidazole salt, 4-aminoimidazole salt or 5-amino-imidazole salt ligand described elsewhere in the present disclosure). For example, the ligand according to the best mode can be a N-containing heterocyclic ring (that is, N and / or NH groups belong to heterocyclic ring structure) containing N and / or NH groups embedded in the heterocyclic ring structure, preferably -N-NH-groups. Examples of such N-containing heterocyclic ring structures include pyridyl, piperazinyl, tetrazolyl, pyrazolyl, triazolyl, pyrrolyl, imidazolyl moieties. As previously mentioned, in the absence of bonding between the basic group and the MOF metal site, the basic group / functional group present in the N-containing heterocyclic ligand, preferably in the form of -N- or -NH-groups embedded in the heterocyclic ring, preferably -N-NH-groups (that is, N and / or NH groups belong to heterocyclic ring structure) can capture aldehydes more sustainably and be stable during thermal regeneration and / or solvent regeneration. Indeed, in the case of basic groups / functional groups bonded to the metal sites of MOFs, there is a risk of their removal during aqueous and / or thermal regeneration. Moreover, in the case of MOFs with basic groups / functional groups covalently grafted to ligands (e.g., formate, carboxylate or -NH 2 Group, preferably -NH 2 Compared to MOFs having at least one additional basic group on the N-containing heterocyclic ligand (such as an amino-imidazole salt ligand) that does not participate in bonding to the metal site of the MOF, such MOFs having N-containing heterocyclic ligands that contain N and / or NH groups, preferably -N-NH- groups, embedded in the heterocyclic structure have the advantage of water stability.
[0096] According to the best mode, the N-containing heterocyclic ligand with -N- and / or -NH- groups embedded in the heterocyclic ring, preferably -N-NH- groups, can be a polycarboxylic acid ligand with -N- or -NH- groups embedded in the heterocyclic ring, preferably -N-NH- groups, and there is no bonding between the -N- or -NH- basic groups and the MOF metal site. The ligand is bonded to the MOF metal site through the carboxylic acid group (thereby forming a MOF three-dimensional structure). Such ligands can be selected from dicarboxylic acids, tricarboxylic acids or tetracarboxylic acid ligands, as allowed by the structure containing the N heterocyclic ring; preferably dicarboxylic acid ligands. For example, the ligand can be a pyridyl, piperazinyl, pyrazolyl, triazolyl, pyrrolyl, imidazolyl ring, which carries at least two carboxylic acid groups covalently bonded thereto. For example, the ligand can be pyrazole-3,5-dicarboxylic acid, pyrazole-3,4-dicarboxylic acid, imidazole-4,5-dicarboxylic acid, imidazole-2,4-dicarboxylic acid, pyrrole-2,5-dicarboxylic acid, pyrrole-2,4-dicarboxylic acid, pyrrole-2,3-dicarboxylic acid, pyrrole-3,4-dicarboxylic acid, pyrazine-2,5-dicarboxylic acid, pyrazine-2,3-dicarboxylic acid, pyridine-2,5-dicarboxylic acid, pyridine-2,6-dicarboxylic acid, pyridine-2,3-dicarboxylic acid, pyridine-2,4-dicarboxylic acid, pyridine-3,4-dicarboxylic acid, pyridine-3,5-dicarboxylic acid, 1,2,3-triazole-4,5-dicarboxylic acid or 1,2,4-triazole-3,5-dicarboxylic acid. For example, the N-containing heterocyclic polycarboxylic acid ligand can be an N-containing heterocyclic dicarboxylic acid ligand, such as:
[0097]
[0098]
[0099] where * indicates the bonding to the MOF metal site.
[0100] When the N-containing heterocycle can only provide one carboxylic acid substituent to bond to the MOF metal site, one of the N atoms present on the N-containing heterocycle can participate in the MOF metal site bond, as long as at least one other N of the heterocycle is not bonded to the MOF metal site. For example, the ligand can be a tetrazolyl carboxylic acid such as
[0101]
[0102] Where * indicates the bonding to the metal site of MOF. In the above tetrazolyl carboxylic acid ligand, the carboxylic acid group and one N atom participate in the bonding to the MOF metal site, while the three basic N atoms embedded in the tetrazolyl heterocycle can still be used for aldehyde VOC adsorption.
[0103] In another variant, an N-containing heterocyclic ligand having -N- and / or -NH- groups, preferably -N-NH- groups, embedded in a heterocyclic ring can be covalently grafted to a polycarboxylic acid ligand or a heterocyclic ligand whose heteroatoms participate in the MOF bonding. For example, the MOF ligand can be selected from a dicarboxylic acid, a tricarboxylic acid or a tetracarboxylic acid ligand; preferably a dicarboxylic acid ligand, which carries a substituent comprising an N-containing heterocyclic ring having -N- and / or -NH- groups, preferably -N-NH- groups embedded in a heterocyclic ring, which group does not participate in bonding to a metal site. For example, such a ligand can have the following structure:
[0104]
[0105] Where * indicates the bonding to the metal site of MOF;
[0106] N-Het represents an N-containing heterocyclic ligand (such as pyridyl, piperazinyl, tetrazolyl, pyrazolyl, triazolyl, pyrrolyl, imidazolyl ring) having an -N- and / or -NH- group embedded in a heterocyclic ring, preferably an -N-NH- group, but not bonded to the metal site of the MOF, and L represents a dicarboxylic acid ligand commonly used in MOFs, wherein L can be an aliphatic or aromatic group.
[0107] Alternatively, the MOF ligand may be a heterocycle that participates in bonding to the MOF metal site, which additionally carries a substituent comprising an N-containing heterocycle having an -N- and / or -NH- group embedded within the heterocycle, preferably an -N-NH- group, which does not participate in bonding to the metal site. For example, such a ligand may have the following structure:
[0108]
[0109] Where * indicates the bonding to the metal site of MOF;
[0110] N-Het represents a N-containing heterocyclic ligand having an -N- and / or -NH- group, preferably an -N-NH- group, embedded in a heterocyclic ring and not bonded to the metal site of the MOF (such as pyridyl, piperazinyl, tetrazolyl, pyrazolyl, triazolyl, pyrrolyl, imidazolyl ring), and L represents a heterocyclic ligand commonly used in MOFs, which is bonded to the MOF metal site via two N atoms (such as the imidazolyl ring in ZIF-type MOFs).
[0111] In the best mode, the ligand of the water stability MOF framework can be selected from dicarboxylic acid, tricarboxylic acid or tetracarboxylic acid ligands; preferably dicarboxylic acid ligands. Preferably, the ligand can carry a basic group (-N or-NH-group, such as-N-NH-group, contained in a pyridyl or oxazolyl core) embedded in the ligand itself or covalently attached / grafted thereon. The example of the oxazolyl core includes the aforementioned N-heterocycle, i.e. pyridine, piperazine, tetrazole, pyrrole, imidazole, triazole, pyrazole. Most preferably, the basic group is embedded in the ligand, but there is no bonding between the basic group and the MOF metal site. The basic group can be in the form of-N or-NH-group, preferably-N-NH-or-NH-, selected from the N-heterocyclic ligand without bonding between the basic group and the MOF metal site. Therefore, the ligand of the water stability MOF framework can also be selected from N-heterocyclic polycarboxylic acid ligands.
[0112] Advantageously, still according to the best mode, the ligands of the water-stable MOF framework can be selected from dicarboxylic acid, tricarboxylic acid or tetracarboxylic acid ligands; preferably dicarboxylic acid ligands, with a basic group as part of the ligand itself, or alternatively as a heterocycle covalently linked to an organic spacer without bonding to any metal (e.g., -N- and / or -NH- groups, preferably -N-NH- groups, contained in a pyridyl or oxazolyl core). In other words, the MOF ligand can be an N-heterocyclic group linked to the metal site via a carboxylic acid group, the N-heterocyclic group containing N and / or NH groups, preferably -N-NH- groups, which do not participate in bonding to the MOF metal site. Alternatively, the MOF ligand can be a ligand commonly used in MOFs, to which is covalently linked / grafted an N-heterocyclic group, the N-heterocyclic group containing N and / or NH groups, preferably -N-NH- groups, which do not participate in bonding to the MOF metal site (e.g., 1,3 BDC-pyrazole, where BDC = benzene dicarboxylic acid).
[0113] Conventional MOF linkers can be C 4 -C 16 A polycarboxylic acid alkyl linker (such as a dicarboxylic acid, a tricarboxylic acid or a tetracarboxylic acid or a carboxylic acid linker, for example C 2 H 2 (CO 2 - ) 2 (fumaric acid), C 2 H 4 (CO 2 - ) 2 (succinic acid), C 3 H 6 (CO 2 - ) 2 (glutaric acid), (C 4 H 4 )(CO2 - ) 2 (Muconic acid), C 4 H 8 (CO 2 - ) 2 (adipic acid)).
[0114] Conventional MOF linkers can be C 6 -C 24 Aromatic polycarboxylic acid linkers, such as benzyl dicarboxylic acid or naphthyl dicarboxylic acid, benzyl tricarboxylic acid or naphthyl tricarboxylic acid or benzyl tetracarboxylic acid or naphthyl tetracarboxylic acid. Advantageously, C 6 -C 24 The aromatic polycarboxylic acid linker, such as benzyl dicarboxylic acid or naphthyl dicarboxylic acid, benzyl tricarboxylic acid or naphthyl tricarboxylic acid or benzyl tetracarboxylic acid or naphthyl tetracarboxylic acid, may be selected from the group consisting of: C 6 H 4 (CO 2 - ) 2 (terephthalic acid), C 10 H 6 (CO 2 - ) 2 (naphthalene-2,6-dicarboxylic acid), C 12 H 8 (CO 2 - ) 2 (biphenyl-4,4'-dicarboxylic acid), C 6 H 3 (CO 2 - ) 3 (benzene-1,2,4-tricarboxylic acid), C 6 H 3 (CO 2 - ) 3 (benzene-1,3,5-tricarboxylic acid), C 24 H 15 (CO 2 - ) 3 (Benzene-1,3,5-tribenzoic acid), C 6 H 2 (CO 2 - ) 4 (benzene-1,2,4,5-tetracarboxylic acid), C 10 H 4 (CO 2 - ) 4 (naphthalene-2,3,6,7-tetracarboxylic acid), C10 H 4 (CO 2 - ) 4 (naphthalene-1,4,5,8-tetracarboxylic acid), C 12 H 6 (CO 2 - ) 4 (biphenyl-3,5,3′,5′-tetracarboxylic acid), and modified analogs selected from the group consisting of 2-methylterephthalic acid, 2,5-dimethylterephthalic acid, tetramethylterephthalic acid, perfluoromethylterephthalic acid, diperfluoromethylterephthalic acid, 2-chloroterephthalic acid, 2-bromoterephthalic acid, 25-tetrafluoroterephthalic acid, tetrafluoroterephthalic acid, dimethyl-4,4′-biphenyldicarboxylic acid, tetramethyl-4,4′-biphenyldicarboxylic acid, dicarboxy-4,4′-biphenyldicarboxylic acid, azobenzene dicarboxylic acid or azobenzene tetracarboxylic acid.
[0115] C listed above 4 -C 16 Polycarboxylic acid alkyl linker and C 6 -C 24 The aromatic polycarboxylic acid linker may be chemically modified to covalently bond a -N- or -NH--containing heterocyclic group (basic group).
[0116] MOF ligands can be any N-containing heterocyclic polycarboxylic acid joints, wherein the N-heterocyclic ring contains -N-NH- groups as part of the ring structure, which do not participate in the bonding of the MOF metal site. For example, the N-heterocyclic ring can be a pyrrole, diazole (e.g., pyrazole or imidazole), triazole or tetrazole, which carries at least two carboxylic acid groups for bonding to the MOF metal site. MOF ligands can be N-containing heterocyclic polycarboxylic acid joints, in the form of 5-membered or 6-membered N-containing heterocyclic groups, such as imidazole, pyrrole, pyrazole, diazole, triazole, tetrazole, which are covalently attached to the organic spacer of the polycarboxylic acid ligand as an organic spacer or alternatively. Preferably, the N-containing heterocyclic joint can be present in the water-stable MOF framework in the form of an N-heterocyclic polycarboxylic acid ligand, with at least one covalently attached thereto, preferably an alkaline group (e.g., -N- and / or -NH-) embedded in the ligand itself.
[0117] Preferably, the -N or -NH- group may be present in the water-stable MOF framework in the form of an N-heterocyclic polycarboxylic acid ligand. For example, the ligand may be pyrazole-3,5-dicarboxylic acid.
[0118] Advantageously, the oxygen-containing species that accept or donate hydrogen bonds in the water-stable MOF framework are present in the form of oxygen-clusters, oxygen-hydroxyl clusters and / or OH.
[0119] Less preferred variants of the ligand:
[0120] The ligand may have a basic group covalently attached thereto (e.g., -NH 2 Groups), which is contrary to the best way that the basic groups (e.g., N and / or NH groups, preferably -N-NH- groups) are embedded in the ligand itself (N-heterocyclic ligand). According to a less preferred variant, the basic group can be in the form of formate, carboxylate or -NH 2 Groups, such as -NH 2 A group (i.e., an aliphatic, heterocyclic or aromatic ligand to which at least one formate, carboxylate or -NH 2 Group, preferably -NH 2 Thus, the ligands of the water-stable MOF framework may also be selected from N-heterocyclic ligands, wherein the N atom constituting the N-heterocyclic ring of the ligand is involved in the bonding to the MOF metal site, and wherein the N-heterocyclic ligand may carry at least one additional basic group (e.g. formate, carboxylate or -NH 2 Group, preferably -NH 2 group), such as an amino-imidazole salt ligand (i.e., NH 2 -imidazolium salt ligand).
[0121] As mentioned above, the MOF linker can be C 4 -C 16 Polycarboxylic acid alkyl linker or C 6 -C 24 Aromatic polycarboxylic acid linkers, although additionally bearing at least one basic group covalently attached to the linker, such as formate, carboxylate or -NH 2 The group (ie as a substituent, contrary to the optimum embedding of a basic group (eg an N and / or NH group, preferably an -N-NH- group) into the ligand itself, such as an N-heterocyclic ligand).
[0122] C listed above 4 -C 16 Polycarboxylic acid alkyl linker and C 6 -C 24 Aromatic polycarboxylic acid linkers can be chemically modified to covalently bond / graft formate, carboxylate or -NH 2 Group (basic group).
[0123] Alternatively, tricarboxylic acid ligands can be used, which are bonded to the MOF metal site via only two of the three carboxylic acid groups, leaving the remaining third available (the carboxylic acid basic group that can be used for VOC capture). UiO-66(Zr)-(COOH) [also known as / named UiO-66(Zr)-BTC] and UiO-66(Zr)-(COOH) 2 That's the situation.
[0124] The MOF linker can be a N-containing heterocyclic linker, wherein the N atom constituting the N-heterocyclic ring of the ligand is involved in the bonding to the MOF metal site, such as a C-containing 3 N-containing heterocyclic linker, such as an imidazolium salt ligand; and additionally having at least one basic group covalently attached thereto (e.g., at least one selected from formate, carboxylate or -NH 2 basic groups), preferably at least one -NH 2 The group is further grafted onto the N-containing heterocyclic linker). For example, the N-containing heterocyclic linker can be a 2-amino-imidazole salt, a 4-amino-imidazole salt or a 5-amino-imidazole salt:
[0125]
[0126] where * indicates the bonding to the MOF metal site.
[0127] Preferably, -NH 2 The group can be present in the water-stable MOF framework in the form of an N-heterocyclic polycarboxylic acid ligand. For example, the MOF ligand can be a polycarboxylic acid with at least one -NH 2 The aromatic polycarboxylic acid ligand of the moiety is such as 2-aminoterephthalic acid, 2-amino-1,4-phthalic acid, 5-aminoisophthalic acid or 5-amino-1,3-phthalic acid.
[0128] Advantageously, the oxygen-containing species that accept or donate hydrogen bonds in the water-stable MOF framework are present in the form of oxygen-clusters, oxygen-hydroxyl clusters and / or OH.
[0129] MOF
[0130] The MOF material can be selected from any MOF known in the art having the following necessary properties:
[0131] -Average pore size (D)< For example Best
[0132] - A hydrophilic core formed by basic groups and oxygen-containing species that accept or donate hydrogen bonds
[0133] - oxygen-containing species that accept or donate hydrogen bonds in the MOF framework, preferably in the form of oxygen-clusters, oxygen-hydroxyl clusters and / or OH
[0134] - Heterocyclic basic groups that are covalently bonded to the MOF ligands but not to the MOF metal sites
[0135] Advantageously, the basic groups participating in forming the hydrophilic core of the MOF are available basic groups embedded in the N-containing heterocyclic ligands, preferably in the form of -N- and / or -NH- moieties, which do not participate in bonding to the metal sites of the MOF, as described in the best mode of the present disclosure.
[0136] Surprisingly, the inventors have discovered that the combination of the above properties achieves the sought after goal of developing an improved air purification system that selectively captures aldehydes such as formaldehyde and / or acetaldehyde. all Desired technical effects. The technical effects achieved, which constitute a significant improvement over air purification systems known in the art, include:
[0137] - A water-stable MOF material;
[0138] - Filtration selectivity and high adsorption capacity (to avoid accelerated saturation phenomena);
[0139] - Adsorption stability under representative environmental conditions (to avoid release / leakage phenomena); and
[0140] - Easy recyclability of the filter media according to protocols readily available to home and professional users (to avoid expensive consumables that often result in poor performance of the air purification media).
[0141] Typically, the MOF can be selected from any of the following crystal structures: MIL-100, MIL-127, UiO-66, MIL-53, MOF-808, MIL-125, MIL-160, MIL-101, ZIF-8, PDA-type MOF materials such as DUT-67 type structures, or CAU-10.
[0142] Of the MOF crystal structures listed above, some may be hydrophobic / amphiphilic and have no basic groups in the structure (e.g., MIL-100 (Fe), MIL-53 (Al)). Other crystal structures may be hydrophilic but have no basic groups in the structure (e.g., MIL-160). Still other crystal structures may be hydrophilic but have basic groups in the ligand structure that are bonded to the metal site (e.g., ZIF-8, where the nitrogen atom of the imidazolate ligand is involved in bonding to the Zn atom of the MOF framework). Therefore, these MOFs will not be suitable for reduction to practice the present invention. However, although this variant is not preferred, the NH 2 Modified forms, or forms in which polar functional groups are covalently grafted onto ligands. Specifically, additional polar basic groups (in the form of formate, carboxylate (e.g., fumarate), -NH 2 The form of a group) can have the following effects:
[0143] - For all the MOFs listed above that may initially be hydrophobic / amphiphilic (before chemical functionalization of the MOF ligands with polar basic groups), Making MOFs sufficiently hydrophilic For use in the present invention;
[0144] - For all MOFs listed above that may initially lack basic groups in their structure (before chemical functionalization of the MOF ligands with polar basic groups), Equipping MOFs with basic groups , which in turn will be available for VOC capture;
[0145] - For all MOFs listed above that may initially have basic groups in their structure that are involved in bonding to the MOF metal sites (before further chemical functionalization of the MOF ligands with polar basic groups), equip the MOF with Available of basic groups, which in turn will be available for VOC capture.
[0146] Generally speaking, the MOF crystal structure includes UiO-66-NH 2 、MIL-53-FA、MOF-808-NH 2 、MIL-125-NH 2 、MIL-101-NH 2 、ZIF-8-NH 2 , Al-3,5-PDA, DUT-67-PZDC, CAU-10-NH 2 , CAU-10-pyridine and CAU-10-pyrazine; or a mixture of two or more thereof; preferably Al-3,5-PDA, MIL-125-NH 2 、UiO-66-NH 2 and CAU-10-NH 2 .
[0147] In general, MOF can be selected from any of the following crystal structures: UiO-66-NH 2 、MIL-53-FA、MOF-808-NH 2 、MIL-125-NH 2 、MIL-101-NH 2 、ZIF-8-NH 2 , Al-3.5-PDA, DUT-67-PZDC, CAU-10-NH 2 , CAU-10-pyridine or CAU-10-pyrazine; or a mixture of two or more thereof; preferably Al-3,5-PDA, MIL-125-NH 2 、UiO-66-NH 2 and CAU-10-NH 2; and (when the MOF crystal structure opens up the possibility of having different types of metal atoms) the MOF metal (metal of the metal ion and / or metal oxide and / or metal hydroxide) can be chosen from a trivalent or tetravalent metal from the rare earth metals (Sc, Y, Tb, Gd, Ce, Ln, La), Ti, Zr, Fe, Al or Cr; preferably Sc, Y, Ln, La, Ti, Zr, Fe, Al or Cr; preferably Ti, Zr, Fe, Al or Cr; more preferably Fe, Al, Ti or Zr, most preferably Al or Zr.
[0148] In general, MOF can be selected from any of the following: UiO-66(Zr)-NH 2 、MIL-53(Al)-FA (“FA” stands for fumaric acid), MOF-808(Zr)-NH 2 、MIL-125(Ti)-NH 2 、MIL-101(Cr)-NH 2 、ZIF-8-NH 2 , Al-3,5-PDA ("MOF-303"), DUT-67(Zr)-PZDC ("PZDC" stands for pyrazole-3,5-dicarboxylic acid), CAU-10(Al)-NH 2 , CAU-10(Al)-pyridine or CAU-10(Al)-pyrazine, or a mixture of two or more thereof. Preferably, the MOF material can be selected from Al-3,5-PDA, MIL-125(Ti)-NH 2 、UiO-66(Zr)-NH 2 or CAU-10(Al)-NH 2 , or a mixture of two or more of the above.
[0149] NH 2 Methods for functionalizing MOFs are known. For example, for NH 2 For functionalized ZIF-8, readers can refer to: KY Cho et al., “Synthesis of amine-functionalized ZIF-8 with 3-amino-1,2,4-triazole by postsynthetic modification for efficient CO2-selective adsorbents and beyond,” J. Mater. Chem. A, Vol. 6, No. 39, pp. 18912-18919, 2018.
[25]
[0150] MOF Best Practices:
[0151] However, in the best mode of implementing the present invention, the preferred MOF crystal structures associated with the above-mentioned best mode ligands include UiO-66, MIL-53, MIL-68, MIL-125, MIL-101, CAU-10, MIL-160, PDA type MOF materials, such as MOF-303, MOF-573 or DUT-67; preferably UiO-66, MIL-53, MIL-68, MIL-101, CAU-10 or PDA type MOF materials, such as MOF-303, MOF-573 or DUT-67; more preferably PDA type MOF materials, such as MOF-303, MOF-573 or DUT-67 type structures.
[0152] Of the MOF crystal structures listed above in the best mode, some may be hydrophobic / amphiphilic and have no basic groups in the structure (e.g., MIL-101 (Cr), MIL-53 (Al)). Other crystal structures may be hydrophilic but have no basic groups in the structure (e.g., MIL-160). Therefore, these MOFs would not be suitable for reduction to practice the present invention. However, the NH 2 Modified forms, or forms in which polar functional groups are covalently grafted onto ligands, will be suitable within the context of the present invention. Specifically, the introduction of additional polar basic groups (in the form of -N or -NH- groups) onto the ligands of these MOFs will have the following effects:
[0153] - For all the MOFs listed above that may initially be hydrophobic / amphiphilic (before chemical functionalization of the MOF ligands with polar basic groups), Making MOFs sufficiently hydrophilic For use in the present invention;
[0154] - For all MOFs listed above that may initially lack basic groups in their structure (before chemical functionalization of the MOF ligands with polar basic groups), Equipping MOFs with basic groups , which in turn will be available for VOC capture;
[0155] - For all MOFs listed above that may initially have basic groups in their structure that are involved in bonding to the MOF metal sites (before further chemical functionalization of the MOF ligands with polar basic groups), equip the MOF with Available of basic groups, which in turn will be available for VOC capture.
[0156] Preferred MOF crystal structures for achieving the best mode include Al-3,5-PDA (MOF-303 or MOF-573), DUT-67-PZDC, CAU-10-pyridine, CAU-10-pyrrole and CAU-10-pyrazine; or a mixture of two or more of the above; preferably Al-3,5-PDA.
[0157] Advantageously, the MOF according to the best mode can be chosen from any of the following crystal structures: Al-3,5-PDA, DUT-67-PZDC, CAU-10-pyridine, CAU-10-pyrrole or CAU-10-pyrazine; or a mixture of two or more of the above; preferably Al-3,5-PDA; and (when the MOF crystal structure opens the possibility of having different types of metal atoms) the MOF metal (metal ion and / or metal oxide and / or metal hydroxide) can be chosen from trivalent or tetravalent metals from the rare earth metals (Sc, Y, Ln), Ti, Zr, Fe, Al or Cr; preferably Ti, Zr, Fe, Al or Cr; most preferably Al or Zr.
[0158] Advantageously, the MOF according to the best mode can be selected from any of the following: Al-3,5-PDA ("MOF-303" or MOF-573), DUT-67(Zr)-PZDC ("PZDC" stands for pyrazole-3,5-dicarboxylic acid), CAU-10(Al)-pyridine, CAU-10(Al)-pyrrole or CAU-10(Al)-pyrazine, or a mixture of two or more thereof. Preferably, the MOF material can be Al-3,5-PDA.
[0159] MOF Literature
[0160] In general, MOFs and the MOF materials mentioned in the various embodiments described in the context of the present invention are known, and their synthesis and characterization have been reported in the literature. In this regard, reference may be made in particular to document WO 2019 / 053048. [6]
[0161] MIL-160(Al) is a known metal-organic framework, for example, as reported in WO 2016 / 186454 and a synthetic method for its preparation. The crystal system of MIL-160(Al) obtained by X-ray diffraction analysis was calculated to have a tetragonal space group of I41md, The a-axis and b-axis lattice lengths and The c-axis lattice length and The unit cell volume <3> (See Figures 1 and Figure 2 ). MIL-160(Al) or Al(OH)[O 2 CC 4 H 2 O-CO 2 ] consists of AlO linked via 2,5-furandicarboxylic acid groups as ligands 4 (OH) 2The octahedrons are composed of spiral cis-shaped chains. All octahedrons are surrounded by oxygen atoms from four ligands and two hydroxyl groups. The -OH ions are in the cis position and connected to the Al center to form chains. These spiral chains extend along the c-axis. The ligands are connected to four octahedrons by two chains. This forms a 3D structure with a partition diameter of about square sinusoidal one-dimensional channels (Permyakova et al., 2017a[7]). The BET area and micropore volume reported by Cadiau et al., 2015[8] are 1070 ± 20 m 2 / g and 0.398±0.005cm 3 / g, while Permyakova et al., 2017b[9] reported a pore volume value of 0.46 cm 3 / g.
[0162] DUT-67(Zr)-PZDC is a known metal-organic framework, for example reported by J. Jacobsen et al., 2018.
[30]
[0163] NH 2 Methods for functionalizing CAU-10 are known. For example, the reader is referred to the work of H. Reinsch et al., 2013.
[26] With regard to CAU-10(Al)-pyridine and CAU-10(Al)-pyrazine, the reader is referred to the report of Cadiau et al., 2015
[40] , which describes a method for preparing CAU-10(Al)-pyridine. CAU-10(Al)-pyrazine can be prepared by a method similar to that described for CAU-10(Al)-pyridine in reference
[40] . CAU-10(Al)-pyrazine and CAU-10(Al)-pyridine correspond to CAU-10(Al) with the ligands pyrazine-2,6-dicarboxylic acid and pyridine-2,6-pyridinedicarboxylic acid, respectively.
[0164] For MIL-125(Ti)-NH 2 Readers can refer to the following reports: Y. Fu et al., 2012
[27] ; and S.-N. Kim et al., 2013,
[28] , which describe the preparation method.
[0165] Advantageously, the MOF may preferably be in a form that allows a large exchange surface between the MOF and the environment in which the volatile organic compounds (in particular aldehydes) must be captured by adsorption. For example, the MOF may be in any conventional form in which the adsorbent can be used for adsorption / desorption purposes, such as but not limited to nanoparticles, powders, films, particles or in the form of composite materials, embedded or applied to the surface of paper or polymers or fibers. For example, document WO2009 / 123484
[10] published in October 2009 discloses a useful method for producing a polyurethane foam filter material with adsorption capacity, which material can be used to support the MOF to implement the present invention. Other examples are the electroplating of polymers containing MOF particles as disclosed in the following documents: M. Rose et al. Adv. Eng. Mater. 2011, 13, 356-360
[11] , R. Ostermann et al. Chem. Commun. 2011, 47, 442-444
[12] , J. Ren et al. Int. J. Hydrogen Energy 2015, 40, 9382-9387
[13] and MR Khan et al. J. Mater. Eng. Perform. 2016, 25, 1276-1283
[14] , which give the final composite fiber material with loaded MOF, simplifying the application of MOF for the adsorption of volatile organic compounds.
[0166] MOF Forming
[0167] Regardless of the preparation method, the MOF that can be used in the reduction practice of the air filtration medium / purification medium according to the present invention can be obtained in the form of powder, nanoparticles or shaped bodies.
[0168] Advantageously, the MOF may be in the form of nanoparticles. Methods for preparing MOF materials in the form of nanoparticles are well known. The reader is particularly referred to the teachings of WO 2009 / 07767
[15] . The MOF nanoparticles may then be shaped into a "shaped body", as further described below.
[0169] Advantageously, the MOFs useful in the context of the present invention may be formed into "molded bodies" (e.g. in the form of pellets, spheres or granules of different shapes / geometries). The production of MOF shaped bodies may be achieved by any suitable method known in the art. For example, these known methods include extrusion or tableting. For example, these known methods include extrusion, slip casting, spark plasma sintering or pressing. In an exemplary embodiment, such a method may include kneading the MOF alone or together with at least one binder and / or at least one pasting agent and / or at least one template compound to obtain a mixture; shaping the resulting mixture by at least one suitable method such as extrusion; optionally washing and / or drying and / or calcining the extrudate; and optionally finishing treatment. The reader is referred to US 2014 / 0213832
[16] and Permyakova A et al. (2017b) [9] for general teachings on the shaping of MOFs by pelletization. Additional teachings may be found in Kim et al. (2015).
[17] In the production of shaped bodies, other materials such as binders, lubricants or other additives may be mixed with the MOF.
[0170] The possible geometries of these MOF shaped bodies are virtually unlimited. Examples are in particular pellets, such as round pellets, pellets, spheres, particles, extrudates such as rods, honeycombs, grids or hollow bodies. Preferably, the MOF can be converted into spherical particles, preferably particles with a diameter of 1 mm to 10 mm, preferably particles with a diameter of 1 mm to 7 mm, more preferably particles with a diameter of 1 mm to 5 mm, most preferably particles with a diameter of 1 mm to 2 mm.
[0171] In another variation, the MOF material can be deposited on a support having filtering capabilities, such as ceramic filter media, glass fiber, paper. The MOF can also be deposited on a support, such as a plate, honeycomb support, grid, or any shape for air purification filter media.
[0172] Advantageously, the resulting shaped MOF will be stable in water (i.e., the beads or other shaped bodies will not turn into powder when in contact with water). From a structural standpoint (at a molecular level), this water stability of the shaped bodies is in addition to the structural water stability of the MOF itself. MOF shaped bodies are said to be water stable if they do not break down into powder when in contact with water.
[0173] The MOFs useful in the context of the present invention can be used as adsorbents in the air filtration medium / purification medium according to the present invention, for example alone or together with other adsorbents or additional materials (i.e. additives commonly used in the manufacture of adsorbent beds, such as binders, lubricants or other additives used in the preparation of molded bodies).
[0174] In another aspect, the present invention provides a method for purifying air, the method comprising contacting the air to be purified with a porous water-stable metal-organic framework (MOF) material, wherein the porous water-stable metal-organic framework material comprises < Preferred The average pore size of the MOF framework, and the hydrophilic core formed by the basic group and the oxygen-containing material accepting or supplying hydrogen bonds, wherein the basic group is covalently bonded to the MOF framework. MOF can be defined as in any variant described in this document. In a more preferred variant, MOF can be defined as in any variant according to the best mode for implementing the present invention (see "ligand best mode" and "MOF best mode" parts described above). Advantageously, water stability MOF can be coated on a carrier in the form of a plate, a honeycomb carrier, a grid or any shape used in an air purification filter medium. Advantageously, water stability MOF can be in the form of a molded body, such as a spherical pellet such as a round spherical pellet, a bead, a sphere, a particle, an extrudate such as a rod, a honeycomb, a grid or a hollow body. Advantageously, the size of the MOF molded body particles can be in the range of particles of 1-10mm diameter, preferably particles of 1mm-7mm diameter, more preferably particles of 1mm-5mm diameter, and most preferably particles of 1mm-2mm diameter. Advantageously, water stability MOF can be made into a molded body using a binder, a lubricant or other additives that are commonly used to prepare an adsorbent molded body. The nature and quantity of the binder can be limited to best impart the water stability of the resulting molded MOF. For example, in contrast to graphite that may be harmful to water stability and / or BET specific surface area, a polymer binder such as polyvinyl butyral or polyvinyl acetate can be used. For example, the water stability of the main body (MOF+ binder) can be achieved by using a polymer binder with a weight % of 1 to 10 weight %, preferably 1 to 5 weight %, and most preferably 1 to 3 weight % based on the gross weight of the MOF+ binder. Advantageously, the binder properties and quantity used will also contribute to achieving an acceptable specific surface area. Similarly, polymer binders such as polyvinyl butyral or polyvinyl acetate may be helpful in this regard, based on the gross weight of the MOF+ binder, preferably 1 weight %-5 weight %, most preferably 1 weight %-3 weight %, and even more preferably 1.5 weight %-3 weight %.
[0175] Advantageously, the shaped water-stable MOF may be contained in the cavity of a hollow support, such as a honeycomb support. Thus, a filtration / purification device may include a hollow support, such as a honeycomb support, filled with a shaped body of the MOF of interest, having the necessary properties as previously described.
[0176] Advantageously, the air purification method may further comprise soaking the MOF material in water and / or a hydroalcoholic solution at room temperature for a suitable amount of time to easily regenerate the water-stable adsorbent MOF material. For example, the method may be used to purify indoor air, such as in a family home, office space, workshop, building, transportation vehicle such as a car, coach, bus, subway, train, airplane, cabin.
[0177] In yet another aspect, the present invention provides a method for preparing a porous water-stable metal-organic framework (MOF) material with improved performance, the porous water-stable metal-organic framework material comprising < Preferred an average pore size of , and a hydrophilic core formed by basic groups and oxygen-containing species that accept or donate hydrogen bonds in the MOF framework, wherein the basic groups are covalently bonded to the MOF framework;
[0178] The method comprises at least one reaction step (i): reacting in a suitable solvent system, preferably a green solvent, preferably water:
[0179] - at least one metal precursor is selected from any one of the following: compounds containing Sc, Y, Ln, La, Ti, Zr, Fe, Al or Cr clusters; preferably Ti, Zr, Fe, Al or Cr; more preferably Fe, Al, Ti or Zr clusters, most preferably compounds containing Al or Zr clusters, such as ZrCl 4 、ZrOCl 2 、ZrOSO 4 、Zr(SO 4 ) 2 , zirconium hydroxycarbonate, ZrO(NO 3 ) 2 、Zr(NO 3 ) 4 、Zr(OR 4 ) 4 、AlCl 3 、Al(NO 3 ) 3 、Al 2 (SO4) 3 、Al(OH) 3 、Al 2 O 3 、Al(OR 4 ) 3 and their corresponding hydrates; wherein R 4 , R 5 and R 6 In each occurrence, H, CO are represented independently 2 , acyl such as Ac, or straight or branched chain C 1-10 Alkyl or C6-10 Aryl moiety; wherein each of the aforementioned aryl moieties may be independently replaced by one or more straight or branched C 1-6 Alkyl or C 6-10 The aryl moiety is further substituted; and wherein each of the aforementioned alkyl moieties may preferably be acyclic;
[0180] - The ligand precursor L' optionally has at least one selected from the group consisting of formate, carboxylate, -NH 2 Or -NH-part of the basic group, wherein at least one basic group is not bonded to the MOF metal site. In the best mode, the ligand precursor L 'is preferably a precursor ligand with N and / or NH basic groups embedded in the ligand, preferably -N-NH-groups (e.g., -NH-groups contained in the pyrazolyl core), such as the N-heterocycle described in the "ligand best mode" section. In a preferred variant, the ligand precursor L can be a polycarboxylic acid counterpart of the polycarboxylic acid ligand L defined in any variant of the best mode for implementing the present invention (see the "ligand best mode" section described above) or any other suitable precursor ligand that can produce a corresponding carboxylate group for bonding to the MOF metal site. Examples of ligand precursors according to the best mode include:
[0181]
[0182] For example, according to the best mode, the ligand precursor L′ can be pyrazole-3,5-dicarboxylic acid, pyrazole-3,4-dicarboxylic acid, imidazole-4,5-dicarboxylic acid, imidazole-2,4-dicarboxylic acid, pyrrole-2,5-dicarboxylic acid, pyrrole-2,4-dicarboxylic acid, pyrrole-2,3-dicarboxylic acid, pyrrole-3,4-dicarboxylic acid, pyrazine-2,5-dicarboxylic acid, pyrazine-2,3-dicarboxylic acid, pyridine-2,5-dicarboxylic acid, pyridine-2,6-dicarboxylic acid, pyridine-2,3-dicarboxylic acid, pyridine-2,4-dicarboxylic acid, pyridine-3,4-dicarboxylic acid, pyridine-3,5-dicarboxylic acid, 1,2,3-triazole-4,5-dicarboxylic acid or 1,2,4-triazole-3,5-dicarboxylic acid.
[0183] As mentioned above, the ligand precursor L′ used in the MOF synthesis may already carry at least one basic group selected from the group consisting of formate, carboxylate, -NH 2 , or N and / or -NH- groups embedded in the ligand itself (e.g., as part of an N-heterocycle). Preferably, the basic groups do not ultimately participate in bonding to the MOF metal sites once the MOF synthesis is complete and the MOF scaffold / framework is formed. Thus, during MOF synthesis, at least one basic group is present in the form of formate, carboxylate, -NH 2Most preferably, according to the best mode, during the MOF synthesis process, at least one basic group is simultaneously introduced into the MOF framework in the form of an -N or -NH- moiety, preferably an -N-NH- group.
[0184] Advantageously, as described above, the ligand precursor L' with at least one basic group can be a ligand precursor that produces a polycarboxylic acid ligand L in the MOF framework once the MOF synthesis is completed. The MOF ligand L can be any of the MOF ligands generally described and any variants herein. In a more preferred variant, the MOF ligand L can be defined as in any variant according to the best mode for carrying out the present invention (see the "Best Mode for Ligands" section described above).
[0185] Typically, the precursor ligand L' may be:
[0186] (i)C 4 -C 16 Polycarboxylic acid alkyl precursor ligands (such as dicarboxylic acid, tricarboxylic acid or tetracarboxylic acid precursor ligands, for example C 2 H 2 (CO 2 H) 2 (fumaric acid), C 2 H 4 (CO 2 H) 2 (Succinic acid) C 3 H 6 (CO 2 H) 2 (glutaric acid), (C 4 H 4 )(CO 2 H) 2 (Muconic acid), C 4 H 8 (CO 2 H) 2 adipic acid)) which additionally carries at least one basic group, such as formate, carboxylate or -NH 2 A group covalently attached to a linker; or other suitable ligand precursors that can produce the corresponding carboxylic acid ligand;
[0187] (ii)C 6 -C 24 Aromatic polycarboxylic acid precursor ligands, such as benzyl dicarboxylic acid or naphthyl dicarboxylic acid, benzyl tricarboxylic acid or naphthyl tricarboxylic acid, or benzyl tetracarboxylic acid or naphthyl tetracarboxylic acid; additionally with a basic group, such as formate, carboxylate or -NH 2 group, preferably with at least one -NH 2A group covalently attached to a linker; such as 2-aminoterephthalic acid, 2-amino-1,4-phthalic acid or 5-aminoisophthalic acid or 5-amino-1,3-phthalic acid; or other suitable ligand precursors that can produce the corresponding carboxylic acid ligands;
[0188] (iii) an N-heterocyclic polycarboxylic acid precursor ligand, such as pyrazole-3,5-dicarboxylic acid, or other suitable ligand precursor that can produce the corresponding carboxylic acid ligand; or
[0189] (iv) N-containing heterocyclic precursor ligands, such as C-containing 3 N-containing heterocyclic precursor ligands, such as imidazole-type precursor ligands; and additionally having at least one basic group covalently bonded to the heterocyclic ring (e.g., at least one selected from formate, carboxylate or -NH 2 The basic group of the group), preferably at least one -NH 2 The group is further grafted onto the N-containing heterocyclic precursor ligand). For example, the N-containing heterocyclic precursor ligand can be 2-amino-imidazole, 4-amino-imidazole or 5-amino-imidazole. 2 This is the case where the two N atoms constituting the imidazolyl heterocyclic ring are involved in the reaction with ZIF-8-NH 2 The metal site (Zr atom) is bonded to the “free” -NH 2 The groups are not bonded to Zr and therefore can still be used to capture aldehyde VOCs such as formaldehyde and / or acetaldehyde.
[0190] Introduction of basic groups after MOF synthesis
[0191] In another variation, the ligand precursor L′ used in the MOF synthesis does not have a formate, carboxylate or -NH 2 In this case, the basic group can be replaced after synthesis with a formate, carboxylate or -NH 2 The MOF framework can be introduced into the form of a moiety. Methods for post-synthetic modification of MOFs are known. These include chemical modification / functionalization of the ligands once the MOF is formed, or the introduction of desired functional groups by alteration of the ligands after the MOF synthesis. For example, for chemical modification / functionalization of ligands on MOFs, the reader is referred to the work of S. Bernt et al., 2011.
[29] For MOF functionalization by alteration of the ligands after the MOF synthesis, the reader is referred to the work reported in KY Cho et al., 2018.
[25] Thus, wherein the ligand precursor L′ does not have at least one formate, carboxylate or -NH covalently bonded thereto 2 part, the method may also include reacting at least one formate, carboxylate or -NH 2 Partially functionalize MOFs; either by ligand exchange or by adding formate, carboxylate, or -NH2 Steps for partial covalent grafting onto MOF ligands.
[0192] Precursor ligand L′ best mode :
[0193] In a most preferred variant, the precursor ligand L' can be a precursor of the ligand L defined in any variant of the best mode for carrying out the invention (see the "Best Mode for Ligands" section described above), i.e., L' can be any suitable precursor ligand that can generate the corresponding ligand L for bonding to the metal site of the MOF during the MOF synthesis. For example, the ligand precursor L' can be:
[0194] (i) an N-heterocycle selected from diazoles (e.g., pyrazoles), triazoles, or tetrazoles with at least two carboxylic acid groups, or other suitable precursor groups that can generate corresponding carboxylic acid groups for bonding to the metal sites of the MOF. The N-heterocycle can be any of the N-heterocyclic structures described in the "Ligand Best Mode" section; for example, the precursor ligand can be pyrazole-3,5-dicarboxylic acid;
[0195] (ii)C 4 -C 16 Polycarboxylic acid alkyl precursor ligands (such as dicarboxylic acid, tricarboxylic acid or tetracarboxylic acid precursor ligands, for example C 2 H 2 (CO 2 H) 2 (fumaric acid), C 2 H 4 (CO 2 H) 2 (succinic acid), C 3 H 6 (CO 2 H) 2 (glutaric acid), (C 4 H 4 )(CO 2 H) 2 (Muconic acid), C 4 H 8 (CO 2 H) 2 (adipic acid)), or other suitable ligand precursors that can produce the corresponding carboxylic acid ligands, which ligand precursors additionally carry at least one N-heterocyclic ring selected from diazole (e.g. pyrazole), triazole or tetrazole, preferably containing an -N-NH- group within the ring structure, the N-heterocyclic ring being covalently attached to the ligand precursor, wherein the N atom of the N-heterocyclic ring does not participate in bonding to the metal site of the MOF;
[0196] (iii)C 6 -C 24Aromatic polycarboxylic acid precursor ligands, such as benzyl dicarboxylic acid or naphthyl dicarboxylic acid, benzyl tricarboxylic acid or naphthyl tricarboxylic acid, benzyl tetracarboxylic acid or naphthyl tetracarboxylic acid; the ligand precursor additionally carries at least one N-heterocyclic ring selected from diazole (e.g. pyrazole), triazole or tetrazole, preferably containing an -N-NH- group within the ring structure, the N-heterocyclic ring being covalently attached to the ligand precursor, wherein the N atom of the N-heterocyclic ring does not participate in bonding to the metal site of the MOF;
[0197] (iv) Heterocyclic precursor ligands whose heteroatoms are intended to bond to the metal sites of MOFs, such as C-containing 3 N-heterocyclic precursor ligands, such as imidazole-type precursor ligands; heterocyclic precursor ligands additionally carry at least one N-heterocyclic ring selected from diazole (e.g., pyrazole), triazole or tetrazole, preferably containing an -N-NH- group within the ring structure, and the N-heterocyclic ring is covalently linked / grafted to the heterocyclic precursor ligand, wherein the N atom of the linked / grafted N-heterocyclic ring does not participate in the bonding of the MOF metal site.
[0198] MOF synthesis can be performed using any MOF synthesis method known in the art. For example, solvent thermal method, mechanical method, microwave method can be used. Advantageously, the reaction can be performed under reflux conditions. Advantageously, the reaction can be performed under reflux conditions for 12 hours to 24 hours.
[0199] The molar ratio of metal precursor / ligand precursor (M / L ratio) can be adjusted according to the final MOF to be prepared (i.e., according to the target MOF structure). For example, the molar ratio M / L=1 to 1.2 can be used for MOF-303, UiO-66-NH 2 and MIL-101-EN. A molar ratio of M / L = 0.10 to 0.15 can be used for ZIF-8. A molar ratio of M / L = 0.30 to 0.40 can be used for MIL-140B.
[0200] advantage
[0201] A major advantage of the above MOFs is that they are specifically designed to selectively remove / capture harmful aldehyde VOCs (volatile organic compounds), preferably short-chain aldehyde VOCs (i.e., 6 carbon atoms or less), such as C1-C2 aldehyde VOCs, such as formaldehyde and / or acetaldehyde, from the air at very low concentrations, even in the presence of high concentrations of water vapor (humid air) and / or in the presence of other VOCs. Short-chain aldehyde VOCs include C6 aldehydes, such as hexanal, which are very commonly used in fragrances and flavors. Typical other short-chain aldehyde VOCs include formaldehyde, acetaldehyde, propionaldehyde, acrolein, benzaldehyde, isopental, pentanal, valeraldehyde, isovaleraldehyde, butyraldehyde and isobutyraldehyde (C4). In a typical indoor environment, formaldehyde and acetaldehyde are the major short-chain aldehyde VOCs, with trace amounts of propionaldehyde, acrolein (C3), benzaldehyde (C6), isovaleraldehyde, valeraldehyde, valeraldehyde and isovaleraldehyde (C5), butyraldehyde and isobutyraldehyde (C4). In terms of the concentration of the most important aldehyde VOCs present in indoor air, C1-C3 aldehyde VOCs represent the majority of short-chain aldehyde VOCs (outside of special indoor spaces with specific controlled gas environments where the VOC composition may be different). Therefore, the present invention is particularly suitable for selectively capturing short-chain aldehyde VOCs, such as C1-C3 aldehyde VOCs, rather than other VOCs (e.g., non-aldehyde VOCs) and water that may be present in the ambient air, even in abnormally humid gas environments (i.e., relative humidity is higher than normal).
[0202] As porous materials, MOFs have generally been used as adsorbents and / or filter materials. However, for the purpose of implementing the present invention, the MOFs described herein, especially the MOFs described according to the best mode, constitute a very special choice of the MOF family. Even in abnormally humid gas environments (i.e., with a relative humidity higher than normal), and in the presence of other VOCs (e.g., non-aldehyde VOCs), they are able to effectively and selectively remove aldehyde VOCs at low concentrations from indoor air, preferably short-chain aldehyde VOCs as described above. In general, in porous materials such as MOFs, competitive adsorption of water (polar molecules) usually hinders the use of general MOFs to adsorb polar volatile organic compounds, such as aldehydes, present in very low concentrations in the air. When the concentration of VOCs to be removed is very low, the presence of water strongly affects the adsorption of polar VOCs.
[0203] The MOFs that can be used in the present invention as described herein, especially the MOFs described according to the best mode, significantly improve the elimination / capture of aldehyde VOCs, preferably short-chain aldehyde VOCs present at very low concentrations (at absolute and relative pressures), even in the presence of high concentrations of water vapor. Therefore, they are chemically and structurally specially designed MOFs for improving the adsorption of aldehyde volatile organic compounds, even when aldehyde VOCs are present at low concentrations in a humid environment (e.g., with a higher than normal relative humidity).
[0204] Thus, the MOFs used in the present invention generally have good water stability and allow selective adsorption of aldehyde volatile organic compounds, preferably short-chain aldehyde VOCs, at very low concentrations. For example, aldehyde selective adsorption can occur at aldehyde concentrations as low as 1 ppb or even lower. In general, the MOFs that can be used in the context of the present invention allow selective adsorption of aldehyde volatile organic compounds present in dry or humid air (i.e., relative humidity ranging from 0% to 100%) at concentrations of the order of 1 ppb and 500 ppm, or even 1 ppb to 100 ppm, below, at or above normal humidity levels comfortable for humans (e.g., below 25% relative humidity, about 25%-30% relative humidity, or >30% relative humidity, such as ≥35% relative humidity, such as ≥40% relative humidity, up to 100% relative humidity). Aldehyde VOCs, especially short-chain aldehyde VOCs, are selectively captured / adsorbed, i.e., the MOFs described herein, especially the specific selection of MOFs described according to the best mode, preferentially capture / adsorb aldehyde VOCs, especially short-chain aldehyde VOCs, rather than other VOCs (e.g., non-aldehyde VOCs) and water that may be present in the surrounding air even in abnormally humid gas environments (i.e., having a higher than normal relative humidity).
[0205] A significant advantage of the water-stable MOF used according to the present invention, in particular the MOF described according to the best mode, is that the captured VOCs, in particular aldehydes, such as short-chain aldehyde VOCs, are not released from the MOF material, even when the temperature is elevated (the typical operating temperature range envisaged is 10°C-50°C), and / or even when the MOF material reaches saturation. In other words, the ingenuity of the present invention lies not only in the selective capture of aldehydes from ambient dry or humid air in the presence of other pollutants, but also in the ability not to release the adsorbed aldehydes even when the temperature is elevated (within the typical operating range of 10°C-40°C, preferably 10°C-50°C). The difference between the MOF material according to the present invention and existing materials (activated carbon, zeolites) is that the "no leakage" storage capacity is not zero and is large enough for widespread commercial use. The "no leakage" property of the filter medium according to the present invention presents a significant advantage over existing filter media, namely the ability to retain aldehydes, such as short-chain aldehyde VOCs, such as formaldehyde and / or acetaldehyde, from the polluted air when it first passes through the filter medium with maximum efficiency, while not releasing aldehydes if the filter medium is saturated. Existing air filtration media / purification systems, particularly carbon filtration media, completely lack both of these properties.
[0206] In particular, the presence of other substances (typically aromatic VOCs such as toluene) does not affect the absorption capacity of the MOFs that can be used in the context of the present invention with respect to aldehyde VOCs, nor their selectivity. This is a further advantage over activated carbon-based filter media / purification media, which are rapidly poisoned by molecules such as toluene (see comparative tests, in particular using Brand activated carbon, and from brand activated carbon / acetoacetamide preparation, described in detail in the Examples).
[0207] The fact that the MOFs envisaged in the context of the present invention selectively adsorb aldehydes, such as formaldehyde and / or acetaldehyde, which are polar organic compounds that are generally soluble in water at the concentrations considered (concentrations of VOCs in air), provides another great advantage, since the MOFs can be regenerated by immersion in water. Optionally, common consumer product additives such as alcohol can be added to the water to improve the regeneration of the MOFs.
[0208] Therefore, in another aspect, the present invention provides a regenerable filter medium for air purification, the regenerable filter medium comprising a porous water-stable metal-organic framework (MOF) material, the porous water-stable metal-organic framework material comprising < Preferred The invention relates to a method for preparing a filter medium having a pore size of 200 μm and a hydrophilic core formed by basic groups and oxygen-containing species that accept or donate hydrogen bonds in the MOF framework, wherein the basic groups are covalently bonded to the MOF framework; wherein the filter medium can be regenerated by washing with water and / or an aqueous alcohol solution. The MOF can be defined in any of the variants described in this document. Particularly preferred MOFs are those described above according to the best mode (see the "ligand best mode" and "MOF best mode" sections).
[0209] In yet another aspect, the present invention provides an air purification system comprising a regenerable filter medium as defined above.
[0210] Based on what has been observed in the case of Al-3.5-PDA according to the interactions between formaldehyde and the active sites (see the Examples, in particular Example 7), the MOFs according to the best mode described in the present disclosure are believed to be regenerable. The MOFs according to the best mode have N-containing heterocyclic ligands having at least one available basic group embedded in the ligand itself, preferably in the form of -N- and / or -NH- moieties, which do not participate in bonding to the metal sites of the MOF. Such ligands are believed to have similar interactions with the active sites (here NNH groups) during formaldehyde adsorption (this has been shown to be the case in the pyrazolidine MOFs Al-3.5-PDA and DUT-67(Zr)-PZDC as well as in the case of imidazoles).
[0211] Naturally, the condition for regeneration is to bring enough energy to the system to destroy the formed interactions (in the case of the interaction between formaldehyde and the -N-NH- groups of the pyrazole ligands, the desorption energy is of the order of 86 KJ / mol). As previously mentioned, the MOF according to the best mode can be regenerated thermally and / or by washing with water and / or hydroalcoholic solutions. This is possible because in the MOF according to the best mode, the energy brought to the system for regeneration does not significantly degrade the structure and active sites of the MOF. In particular, the MOF according to the best mode described herein has one or both of the following properties:
[0212] - the thermal stability of the structure and active sites of the MOF in the temperature range considered for thermal regeneration; and / or
[0213] - Stability of the structure and active sites in water regenerated by washing.
[0214] Furthermore, it has been found that, according to the optimal regime, formaldehyde adsorption does not significantly, if at all, degrade the structure and active sites of the MOF.
[0215] In summary, the reproducibility of MOFs according to the best mode is based on the following findings: in addition to structural stability and active sites in water or aqueous solvents, MOFs according to the best mode have a minimum thermal stability range of the order of about 100°C for the structure and active sites as described herein.
[0216] Gas advantages may also become apparent to those skilled in the art upon reading the following examples with reference to the accompanying drawings, which are provided as non-limiting illustrations.
[0217] Equivalent form
[0218] The following representative examples are intended to help illustrate the present invention, but are not intended to and should not be construed as limiting the scope of the present invention. In fact, various modifications of the present invention and many other embodiments thereof, except those shown and described herein, will become apparent to those skilled in the art from the full content of this document, including the following examples and the references of the scientific and patent literature cited herein. It should also be understood that the contents of those cited references are incorporated herein by reference to help illustrate the prior art.
[0219] The following examples contain important additional information, exemplification and guidance that may be applicable to the practice of the present invention in its various embodiments and their equivalents.
[0220] Example
[0221] The MOF materials and compositions of the present invention and their preparation can be further understood by illustrating some embodiments of methods of preparing or using these MOF materials and compositions. However, it should be understood that these embodiments do not limit the present invention. Variants of the present invention now known or further developed are considered to fall within the scope of the present invention as described herein and claimed below.
[0222] Example 1: Material Synthesis
[0223] 1.1. Al-3,5-PDA :
[0224]
[0225] Gram-level program : 6.00 mmol of 3,5-pyrazoledicarboxylic acid monohydrate and 6.00 mmol of Al(OH) 3 H 2O was introduced into a 100 ml flask (M / L ratio equal to 1). 60 mL of distilled water was added, and the mixture was then placed at 100° C. for 18 hours under stirring. After filtration, the white solid was washed in 60 ml of distilled water at 100° C. for 5 hours, then filtered again and dried in an oven at 100° C. for 2 hours. (Specific surface area (BET) is about 1343 m 2 / g and a pore volume of 0.49 cm 3 / g) (yield: 1.47 g of Al-3,5-PDA, taking into account 44% water loss, resulting in a 54% yield based on the linker).
[0226] Amplification Program : 156g (2mol) aluminum hydroxide (Al(OH) 3 xH 2 0) and 347 g (2 mol) of 1H-pyrazole-3,5-dicarboxylic acid and 20 liters of distilled water were heated to 100° C. under stirring. After 18 hours of reaction, a white solid was recovered by Büchner filtration. The solid was again placed in 20 liters of distilled water for 5 hours and then filtered again.
[0227] According to Farhad Fathieh et al. The synthesis was carried out according to the protocol in (Sci. Adv. 2018; 4: eaat3198, pp. 1-9.
[18] ): 5.2 g of aluminum chloride hexahydrate (AlCl 3 *6H 2 O, 21.54 mmol) and 3.75 g 3.5-pyrazoledicarboxylic acid monohydrate (H 2 PZDC, 21.54 mmol) was dissolved in 360 mL of water in a 500 mL glass jar, and 15 mL of NaOH aqueous solution (1.3 g, 32.5 mmol) was added dropwise to the mixture under stirring. The vial was then sealed and heated in a 100 °C constant temperature oven for 24 h. BET specific surface area = 1380 m 2 / g; pore volume = 0.55 cm 3 / g.
[0228] 1.2. MIL-101(Cr)-ED (MIL-101(Cr) grafted with ethylenediamine groups on MOF metal sites) - Comparative Example
[0229] MIL-101(Cr) was prepared by mixing terephthalic acid (166 mg, 1 mmol), Cr(NO 3 ) 3 .9H 2O (400 mg, 1 mmol), HF (0.2 mL, 1 mmol) and deionized water (4.8 mL, 265 mmol) were heated to 220°C for 8 h, as disclosed in the document G. Férey et al. Science 2005, 309, 2040-2042
[19] . After cooling the autoclave, the green powder can be taken out and washed. Removal of a large amount of excess unreacted terephthalic acid from the powder is carried out by following this purification method. First, the solution is filtered twice using a glass filter medium with a pore size of 40 μm to 100 μm to remove insoluble terephthalic acid from the solution. Then, the product is placed in an autoclave and washed with ethanol at 80°C for 24 h. After this step, the solid is mixed with 1 M NH 4 F solution for 24 hours, then filtered and washed with hot water. The resulting product was then dried at 150 ° C overnight.
[0230] After heating 0.5 g of MIL-101 (Cr) at 150 ° C for 12 h, the solid was suspended in 30 mL of anhydrous toluene, as disclosed in the document YK Hwang et al. Angew. Chem. Int. Ed. Engl. 2008, 47, 4144-4148
[20] . Ethylenediamine (0.05 mL, 0.75 mmol) was then added to the suspension and stirred at reflux for 12 h. After the reaction, the material was filtered off, washed with deionized water and ethanol, and dried at room temperature (i.e., in this example, at a temperature between 18 ° C and 28 ° C).
[0231] Functionalization of MIL-101(Cr) with ED increases the formaldehyde uptake capacity (leakage-free and total uptake) compared to MIL-101(Cr). However, there is a high risk that the ED grafted onto the metal sites will be removed during regeneration by immersion in water and / or hydroalcoholic solutions. For this reason, MIL-101(Cr)-ED is not desirable in the context of the present invention. Furthermore, MIL-101(Cr)-ED does not belong to the claimed invention because (i) it has a porosity greater than 10 angstroms and also because (ii) the ED is grafted onto open metal sites instead of onto organic ligands.
[0232] 1.3.MIL-101(Cr)-NH 2 (with grafted NH 2 MIL-101 (Cr) of the group) - Examples provided for reference only
[0233] MIL-101(Cr)-NH 2 Can pass MIL-101(Cr)-NO 2 Prepared from MIL-101(Cr), for example according to the method reported by S. Bernt et al.
[29]
[0234] Compared with MIL-101(Cr)-ED, MIL-101(Cr)-NH 2 , because of its hydrophilic nature and the basic groups (NH 2 ), the ligand does not bond to the MOF metal site and can therefore be used to capture VOCs, such as aldehydes (e.g. formaldehyde and / or acetaldehyde). However, this is not a preferred variant.
[0235] 1.4. ZIF-8 - Comparative Example
[0236] First, Zn(NO 3 ) 2 .6H 2 O (2.933g, 9.87mmol) was dissolved in 200mL methanol. The same operation was performed on the ligand by placing 2-methylimidazole (6.489g, 79.04mmol) in 200mL methanol, as disclosed in the document A. Demessence et al., Adsorption properties in high optical quality nanoZIF-8thin films with tunable thickness, J. Mater. Chem., 2010, 20, 7676-7681
[21] . After the substance was dissolved, the solution with the metal was quickly poured into the ligand mixture under stirring at room temperature (i.e., in this embodiment, at a temperature between 18°C and 28°C). Slowly, the solution became less transparent. After 1h, the reaction was stopped and the solid was separated from the liquid by centrifugation at 20000rpm for 15min. The particles were then washed with anhydrous ethanol and centrifuged three times to remove excess unreacted salt and ligand. The solid was then dried overnight at room temperature (i.e., in this embodiment, at a temperature between 18°C and 28°C).
[0237] 1.5.ZIF-8-NH 2 (Having a grafted NH 2 The examples provided for reference only are ZIF-8 of the group
[0238] ZIF-8-NH 2 Can be prepared from ZIF-8, as reported by Cho et al.
[25]
[0239] In contrast to ZIF-8, in which the basic nitrogen atoms on the imidazolium ligands are involved in bonding to the Zr metal site, ZIF-8-NH 2 , because there are additional basic groups (NH 2), and can therefore be used to capture VOCs, such as aldehydes (e.g., formaldehyde and / or acetaldehyde). However, this is not a preferred variant.
[0240] 1.6.UiO-66(Zr)-NH 2 : Examples provided for reference only
[0241] Prepare ZrCl in 3 mL DMF 4 (233 mg, 1 mmol) and 2-aminoterephthalic acid (181 mg, 1 mmol) were added to a 23 mL Teflon pad, as disclosed in the document C. Gomes Silva et al. Chem. Eur. J. 2010, 16, 11133-11138
[22] . The mixture was heated in an oven at 100°C for 24 h. The solid was then recovered after filtration and treated with DMF. The material was then placed in DMF under stirring overnight at room temperature (i.e., in this example, at a temperature between 18°C and 28°C). After a new filtration, the solid was washed twice with THF and dried at room temperature (i.e., in this example, at a temperature between 18°C and 28°C). However, this is not a preferred variant.
[0242] 1.7.MIL-140B(Zr)- Compare Comparative Examples :
[0243] In a 500 mL round-bottom flask, ZrCl 4 (2.77 g, 11.9 mmol), 2,6-naphthalenedicarboxylic acid (7.08 g, 32.8 mmol) and acetic acid (25.5 mL, 450 mmol) were mixed in 430 mL DMF and kept at reflux for 7 h. The solution was then filtered and the resulting solid was washed with 200 mL DMF at 120 ° C for 2 h30, then filtered, and finally washed with 400 mL MeOH for 12 h to obtain the material of interest, MIL-140B.
[0244] Example 2: Material Characterization
[0245] Three series of analyses have been performed to confirm the availability and characterize the various materials synthesized in Example 1:
[0246] --Nitrogen adsorption at 196℃;
[0247] - PXRD pattern of the synthesized material; and
[0248] -Thermogravimetric analysis of synthesized materials.
[0249] 2.1 Nitrogen adsorption at -196°C: Nitrogen (air liquid, 99.999%) adsorption-desorption isotherms at -196°C were measured in a volumetric automatic device (Micromeritics, ASAP2010) using a liquid nitrogen cryobath. Prior to the measurement, the sample was degassed at 150°C at a pressure below 0.133 Pa for 8 h.
[0250] 2.2 PXRD patterns of synthesized materials: X-ray powder diffraction patterns were obtained using a high resolution D5000 Siemens X'Pert MDP diffractometer (λCu, Kα1, Kα2) in continuous mode from 5° to 20° (2θ) using a step size of 0.02° and 10 s accumulation / step.
[0251] 2.3 Thermogravimetric analysis of the synthesized materials: To obtain the TGA curve of each synthesized material, the sample (about 10 mg) was analyzed at a constant rate of 2°C / min in air using a gravimetric analyzer (model Perkin Elmer STA 6000).
[0252] All results of these analyses confirmed the availability of the various materials synthesized in Example 1.
[0253] Example 3: MOF molding
[0254] The molded body was prepared by a wet granulation method. The solid Al-3,5-PDA obtained in the above Example 1.1 was mixed with 2% by weight of polyvinyl butyral (PVB). The wetting process was carried out using ethanol sprayed into the mixture. The mixture was then manually processed to obtain spherical particles with an average diameter of 1.4 mm to 2 mm. Finally, the molded body was placed in a vacuum oven at 130°C for 4 hours.
[0255] Note: In the final step (vacuum drying), increasing the temperature to 250°C-400°C can help increase the mechanical strength and water resistance of the molded body.
[0256] The same protocol was repeated by varying the weight of binder and the binder itself, see Table A below: Water stability of the host (MOF + binder) was achieved by using wt% polymer binder ranging from 1 wt% to 10 wt%. Acceptable specific surface area was achieved by using 1.5 wt% to 3 wt% polymer binder. Using higher wt% polymer binder may result in partial locking (or blocking) of the pores. No structural changes were observed from FT-IR and PXRD spectra.
[0257] Table A
[0258]
[0259]
[0260] nd: Undetermined
[0261] Example 4: Air Filter Media
[0262] 17x16.3x1cm 3 The honeycomb filter medium was filled with the molding material prepared in Example 3 and tested in the conventional mode.
[0263] Example 5: Experiment on the aldehyde adsorption capacity of different test adsorbent materials
[0264] The formed MOF materials (pellets) were tested using a syngas test bench equipped with advanced analytical equipment, which constitutes a set of operational analyses. The term “operational” refers to the study of the catalyst (or adsorbent) in operation, i.e., in an environment similar to the real environment of the material under working conditions, by coupling spectroscopic techniques with tools for quantifying the functional efficiency of the material
[23] .
[0265] The operating systems used are:
[0266] - A stand for supplying different gases, which allows to establish the flow of reagents. A set of mass flow meters precisely controls each gas flow forming the reaction mixture. All mass flow meters are controlled by a user interface. A thermostatic bath (in which a saturator is arranged) allows water to be fed to the system in gaseous form ( Figure 8 and Fig. 9 ).
[0267] - Operating unit, which consists of a sample holder, several stainless steel metal parts, a thermal resistor, a cooling system, a potassium bromide (KBr) window and a thermocouple. The sample is placed in the unit through the sample holder. The KBr window ensures the tightness of the whole and, due to its transparency in the IR, allows to obtain the infrared spectrum of the material surface. The reaction flow reaches perpendicular to the infrared beam to the edge of the wafer, passes through the wafer being tested and is then sent to all the analyzers. The thermal resistor allows the temperature of the unit to be increased (from room temperature to a maximum of 600°C-800°C, depending on the model). The temperature is monitored by thermocouples. Finally, the cooling system avoids the risk of overheating, which could cause irreparable damage to the external parts of the unit and to the sample ( Fig. 9 ).
[0268] - Mass spectrometer (OmniStar GSD 320). The latter allows real-time quantification of different reaction species or products by measuring different previously selected representative masses.
[0269] -Infrared spectrometer (Nexus Thermo-Nicolet-6700), controlled by OMNIC FTIR software, whose MACRO basic function allows the alternating acquisition of surface and gas phase infrared spectra.
[0270] Experimental plan
[0271] The purpose of the operation protocol was to study the adsorption efficiency of the various tested MOFs according to the invention in operation under flow, in different situations close to the actual operation of the purification / filtration / filtration system.
[0272] About 20 mg and 2 cm 2 The molding material is inserted into the operating unit.
[0273] Two gas flows were used: an activated flow for formaldehyde release studies (total flow: 20 cc / min, 20% O 2 +Ar) and reaction flow for formaldehyde adsorption / absorption (total flow rate: 20cc / min, 20% O 2 +415ppm formaldehyde +N 2 ).
[0274] Formaldehyde is produced by a liquid mixture of formaldehyde and water (formaldehyde 16 wt %) placed in a saturator. The system allows one of the two streams to be sent to the unit, and the other stream is sent directly to the analyzer to have an internal standard for accurate quantification in the system. The flow change is carried out by a six-way valve that allows rapid alternation between the activation stream and the reaction stream to observe the adsorption phenomenon of the sample without interference caused by the stability of different MOF materials. Therefore, in this embodiment, the sum of two streams (activation and reaction) is analyzed simultaneously by gas phase IR spectroscopy and mass spectrometry. This makes it possible to check the stability of various MOF materials at the beginning of the reaction and also to have a reference level of formaldehyde at each moment.
[0275] The molded MOF sample was placed under the activation flow in advance, which stabilized the reaction flow. After stabilization, the sample was placed under the reaction flow (total flow rate: 20 cc / min, 20% O 2 , +415ppm in N 2 This is the step of adsorbing the material. The MOF is placed in the reaction stream until it is completely saturated.
[0276] In the mass spectrometry analysis, the formaldehyde content is followed by the change in mass 29 (28 and 30). During the adsorption period, the amount of formaldehyde present in the flow decreases, which corresponds to the decrease in mass 29 (28 and 30). Gradually, as the MOF material begins to saturate, the amount of formaldehyde present in the reaction flow increases, and mass 29 (28 and 30) also increases. Finally, the amount of formaldehyde and mass 29 (28 and 30) present in the pipeline return to the initial introduction level, and the material is then saturated. It was also detected by gas phase FTIR spectroscopy at the CH bond 2781-2778cm -1The changes in the amount of formaldehyde are monitored within the range of the elongational vibrations of the sample. During the adsorption, the characteristic peak of formaldehyde initially decreases and then increases to its initial intensity. Thanks to the calibration previously carried out, it is also possible to correlate the amount of formaldehyde present in the gas phase at each moment by considering the air of the formaldehyde peak in the FTIR spectrum of the gas phase. The maximum adsorption capacity is determined by analysis of the mass spectral mode, more specifically by integrating the curve into the negative of the mass 29 corresponding to the total amount of formaldehyde adsorbed by the sample.
[0277] After saturation, the desorption step was performed. The sample was placed under an activation flow (total flow rate: 20 cc / min, 20% O 2 +Ar). If the MOF material releases formaldehyde at room temperature, an increase in the baseline level of line 29 in the mass spectrum and an increase in the peak characteristic of formaldehyde in the infrared gas phase spectrum should be observed. The end of desorption is recorded by returning to the initial state of mass 29 in the mass spectrometry and the characteristic peak of formaldehyde in the infrared gas phase spectrum.
[0278] Still under the activation flow, desorption was studied at different temperatures representing dwell conditions or representing conditions during thermal regeneration: 23°C, 25°C, 30°C, 35°C, 45°C, 50°C, 75°C, 100°C, 150°C, 200°C. The temperature ramp was 3°C / min. The samples were placed at different temperatures for the time required to restore equilibrium. After the first reactivation, the MOF material was saturated with formaldehyde again and then placed under the activation flow, this time loaded with 90% relative humidity. The second adsorption was used as a check.
[0279] Results
[0280] In various operational studies, different material parameters explaining formaldehyde adsorption were investigated with the aim of subsequently searching for other potential adsorbents. Therefore, a number of MOF samples with various properties were tested (see Figure 1). Two commercial reference materials were also included in the study as comparative examples: Blue Brand activated carbon, and from Brand of activated charcoal / acetoacetamide preparation.
[0281] The results are shown in FIG10 , where “Al-3,5-PDA 1st” corresponds to the sample with 980 m 2 The results obtained for the first synthesized Al-3,5-PDA material with a specific surface area BET of 1300 m / g, while the "optimized Al-3,5-PDA" corresponds to the results obtained after optimization of the synthesis, as detailed in Example 1.1 (BET of 1300 m / g). 2 / g).
[0282] The background color in Figure 10 varies in shade depending on the hydrophobic / hydrophilic properties of the MOF. A lighter background indicates a MOF with hydrophobic properties, while a darker background indicates a more hydrophilic MOF.
[0283] Tables 1A-D (collectively referred to as "Table 1") show the various results obtained during the co-adsorption of formaldehyde and water under the above conditions.
[0284] Table 1: The results of the experiment on the influence of 20% O 2 , 90% RH and 415 ppm formaldehyde at a flow rate of 20 cc / min (the no-leak adsorption capacity corresponds to the amount of formaldehyde adsorbed by the sample during 100% filtration in formaldehyde).
[0285]
[0286]
[0287] (a) The comparative MOF UiO-66(Zr)-2(CF) was prepared according to the protocol described in reference [391 3 ).
[0288] Generally, high specific surface area and pore volume of adsorbents with microporosity favor formaldehyde adsorption. However, the chemical properties of the adsorbent surface are the most important parameters. In particular, the diagram makes it possible to establish a link between the hydrophilicity of the various materials and their maximum formaldehyde adsorption capacity. The hydrophobic materials used, ZIF-8, UiO-66(Zr)-2(CF 3 ) and MIL-140B are ineffective for adsorption of formaldehyde. This can be explained by the chemical properties of formaldehyde and in particular its hydrophilicity. However, Table 1 shows not only convincing hydrophilicity, as shown by experiments conducted on MIL-160 (A1), which is a very hydrophilic material and adsorbs a moderate amount of formaldehyde.
[0289] The presence of amine groups promotes the adsorption of formaldehyde. 2 、UiO-66(Zr)-NH 2 The adsorption performance of formaldehyde on MIL-53(Al)-NH 2 The exception is that its formaldehyde adsorption capacity is lower than that of MIL-53(Al), which can be explained by the fact that the amine groups tend to block the structure of the material in a “very narrow pore” conformation or by the infinite chain of amine groups with MIL-53(Al) [AlO 6 ] ∞ This has the dual effect of making the amine bond unavailable and making the structure narrower, where the pore size is insufficient to accommodate formaldehyde within the pore. 2The amine groups in MIL-53(Al)-NH 2 Therefore, this MOF is not considered to fall within the scope of the present invention.
[0290] Lewis acid and Brüningster acid sites appear to play a major role. In the Lewis point of view, an acid is a substance with an electron gap, which makes it possible to accept an electron pair, in the case of MOFs, they are unsaturated coordination sites (CUS: coordinated unsaturated sites). In the sense of Brüningster, an acid is a substance that is able to produce a proton, usually with a hydroxyl group, in the MOF structure. Lewis acid sites are usually obtained after thermal activation of the sample at high temperatures (100°C-200°C), because residual water must be removed to make it accessible. This example reveals a small difference between the maximum formaldehyde adsorption capacity between thermally activated and non-thermally activated materials. The relative humidity in the reaction stream is high enough to convert the Lewis acid sites generated during thermal regeneration of the sample back into Brüningster acid sites. Brüningster acid sites play a role in the adsorption of formaldehyde. More specifically, amine groups and free pyrazoles, i.e., groups that are not attached to the metal ions of the MOF framework, as in the case of the most effective materials, Al-3,5-PDA and DUT-67(Zr)-PZDC, two materials with different structures but synthesized using the same ligand (pyrazole-3,5-dicarboxylic acid).
[0291] Table 2 summarizes the adsorption capacities of the selected MOF samples, which show great promise compared to conventional filtration materials (activated carbon).
[0292] Table 2: Formaldehyde and water at 23°C in a 20% O 2 , 90% RH and a flow rate of 20 cc / min consisting of 415 ppm formaldehyde. For each adsorbent tested from left to right: (i) no-leak formaldehyde adsorption capacity, (ii) maximum formaldehyde adsorption capacity, (iii) maximum water adsorption capacity, (iv) operating days. To determine the operating days, the results of maximum formaldehyde adsorption were extrapolated to the case when 100 g of filter media was used. The apparatus was purged with 100 m3 of contaminated formaldehyde at a concentration of 0.1 ppm. 3 / h stream.
[0293]
[0294] Leak-free adsorption corresponds to the fact that no adsorption of formaldehyde particles is detected at the outlet of the operating unit (100% filtration in formaldehyde). This can occur by filling specific sites with a high affinity for formaldehyde, interacting with pyrazole groups in the case of Al-3,5-PDA and DUT-67(Zr)-PZDC MOFs. It should also be noted that MIL-101(Cr) has a very low leak-free adsorption compared to its counterparts due to the absence of specific sites, except for the Lewis acid sites that are competitively consumed by water. Its rather high maximum adsorption is due to its large specific surface area (>3000 m 2 / g). In addition, activated carbon has zero leakage adsorption.
[0295] Table 3 shows the formaldehyde released from various samples by gradually increasing the temperature from ambient temperature. Regarding Al-3.5-PDA and DUT-67(Zr)-PZDC, there is no formaldehyde release near ambient temperature.
[0296] Table 3: The amount of formaldehyde released in percentage by each test material by increasing the temperature in 30 minute increments at a 20 cc / min flow consisting of argon and 20% oxygen.
[0297]
[0298] Table 4: Acetaldehyde at 23°C in 20% O 2 , 0% RH and 700 ppm acetaldehyde under the conditions of 20 cc / min flow rate. For each adsorbent tested from left to right: (i) no-leak acetaldehyde adsorption capacity, (ii) maximum acetaldehyde adsorption capacity, (iii) maximum water adsorption capacity, (iv) number of operating days with 100% pollutant removal efficiency.
[0299]
[0300] Additional adsorption studies were performed by subjecting various samples to flows consisting of different pollutants (acetaldehyde, formaldehyde and toluene). Table 5 shows the different results obtained. The adsorption of formaldehyde and acetaldehyde was preferential, formaldehyde being most selectively adsorbed compared to toluene. We observed that the reduction in formaldehyde adsorption performance could be caused by a very partial blocking of the surface porosity by toluene, an effect that was more pronounced in the case of the total formaldehyde adsorption capacity of the activated carbon divided by 4, compared to the case of the adsorption of formaldehyde and water only. The results show that Al-3,5-PDA has a very specific capture efficiency for formaldehyde, thanks to the chemical adsorption method described in Example 7.
[0301] Table 5: Co-adsorption in the case of a pollutant mixture. The flow rate was 20 cc / min, consisting of 20% oxygen and 452 ppm formaldehyde, 300 ppm acetaldehyde, 300 ppm toluene and 70% relative humidity.
[0302]
[0303] In situ IR analysis
[0304] In situ IR analysis was performed to evaluate the absorption / adsorption pattern of formaldehyde in porous solids, especially in the most effective Al-3,5-PDA. (See Fig.11 )
[0305] When a certain dose of formaldehyde is adsorbed onto Al-3,5-PDA solid, the peaks at 3368-3295 and 3724-3661 cm -1 The NH and OH bands of solid extension vibrations gradually disappear in the region, favoring the bands at 3295-3041 and 3659-3455 cm -1 Hydrogen bonds are formed in the corresponding regions of the ligand (Figure 1). This may indicate adsorption of the molecule via the oxygen on the hydroxyl and amine protons of the ligand and via the hydrogen atom on the electron-free nitrogen of the ligand.
[0306] Example 6 - MOF regeneration by water washing
[0307] To test the new regeneration by immersion in water, formaldehyde adsorption and subsequent regeneration by washing cycles were performed. Formaldehyde adsorption was performed as described in the previous protocol, except for thermal reactivation. Instead, the MOF pellets were placed in a flask containing 100 mL of distilled water and stirred overnight at room temperature. After this operation, the solid was recovered in powder form, filtered on a Büchner and dried at room temperature and pelletized again (molded into pellets) for formaldehyde adsorption. This procedure was repeated a second time.
[0308] Table 6 shows the Al-3,5-PDA material prepared in Example 1.1 and Blue during the saturation / washing cycle in water. Comparative amounts of formaldehyde adsorbed by activated carbon of . The regeneration of the samples after adsorption of formaldehyde by immersion in water can be explained by the solubility of formaldehyde in water. However, after the second wash, the formaldehyde adsorption capacity decreased by about 14% and 20% in the case of Al-3,5-PDA and activated carbon, respectively. These values fall within the error range of the experimental results of + / -10%, however the adsorption capacity has a decreasing trend, which may mean that the material is not fully regenerated. However, the performance of the MOF material in formaldehyde capture remains essentially intact and outperforms the reference. Additional washing tests were performed on 75 mg Al-3,5-PDA with 2% PVB using the following regeneration protocol: quenching in 500 mL hot water (50°C) for 3 hours, followed by rinsing with 2 liters of hot water (50°C). No significant changes in the adsorption capacity (no leakage and maximum formaldehyde adsorption capacity) were observed over the 5 adsorption / regeneration cycles. This can be explained by increasing the amount of sample used, which does reduce the measurement error. The solubility of formaldehyde in hot water also increases.
[0309] Table 6: Amount of formaldehyde adsorbed by immersion in water during different adsorption / regeneration cycles.
[0310]
[0311] "Real" Testing Using Air Filter Media
[0312] A comprehensive test was carried out. The analysis system consists of a test section, a syringe conditioned in ODC (Opening Operation Cycle, "RCO" in French, meaning "Opening Cycle Report"), allowing the injection of the pollutant in liquid form previously placed in a sealed container. The latter is placed under a pressure of 3 bars and the line connecting the test section and the container containing the pollutant is heated to 100 ° C. The gaseous pollutant is sent to the test area to obtain a stable operating flow rate and gas composition. The polluted air flow is continuously in contact with different filter media, the dimensions of which are 17x16.3 cm 2 The concentration of various pollutants at the system output was measured by Fourier Transform Infrared Spectroscopy and interpreted over time.
[0313] The overall experiment was conducted as follows:
[0314] Pre-adsorption of toluene and xylene was carried out for 15 minutes, then after changing the liquid in a sealed chamber, adsorption of formaldehyde and acetaldehyde was carried out for 15 minutes. The adsorbent material was then placed in water for a regeneration step, after which it was again placed under a flow of toluene and xylene, then in aldehydes, then in water and so on, until the result was obtained after the third wash. The concentrations used are summarized in the following table:
[0315] Table 7
[0316]
[0317] Comprehensive experiments show that Blue The activated carbon filter media deactivated after the first adsorption of aromatic compounds (toluene and xylene). After saturation with toluene and xylene, the activated carbon was no longer able to adsorb other VOCs or to regenerate by immersion in water (Tables 8 and 9). On the other hand, the filter media with Al-3,5-PDA did not adsorb aromatic compounds, would preferentially adsorb formaldehyde from a formaldehyde and acetaldehyde mixture, and appeared to regenerate by immersion in water. The affinity of activated carbon for hydrophobic molecules such as aromatic compounds could explain this behavior. In addition, the adsorbed aromatic compounds may tend to enhance the hydrophobicity of the system and thus prevent water from diffusing into the pores, which could prevent regeneration.
[0318] Table 8: Amount of toluene and xylene adsorbed on activated carbon filter media and Al-3,5-PDA filter media after "full" adsorption and washing by immersion in water.
[0319]
[0320] Table 9: Amount of formaldehyde adsorbed on activated carbon filter media and Al-3,5-PDA filter media after "full" adsorption and washing by immersion in water.
[0321]
[0322] Example 7
[0323] 7.1 Introduction
[0324] The purpose of the following examples was to study and understand the interaction modes occurring during the adsorption of gaseous formaldehyde on pyrazolidine-based metal-organic frameworks, where embedded basic groups (-HN or -N) are accessible.
[0325] The following results demonstrate that the adsorption of formaldehyde occurs via chemisorption of formaldehyde. The host-guest interaction occurs via the formation of a covalent bond between the pyrazolyl linker and the formaldehyde; this is further stabilized by hydrogen bonding, leading to the formation of a stable oxy-methyl species. The same type of interaction occurs in the case of two MOFs carrying free accessible pyrazole groups within their pores, namely Al-3.5-PDA and DUT-67(Zr)-PZDC, and with imidazole species (ligands only, no MOFs to date). The desorption energy characterizing the type of interaction was estimated using the Redhead method
[42] and was found to be in the range of 86 kJ / mol, providing sufficient stability to provide low formaldehyde release under humid air. With amino-aromatic metal carboxylate MOFs such as UiO-66(Zr)-NH 2 / MIL-125(Ti)-NH2 This is a significantly improved step compared to MIL-101(Cr)-ED, which tends to release some formaldehyde at near-ambient temperatures due to the formation of some unstable adsorbed species and will be degraded by moisture in the case of MIL-101(Cr)-ED.
[0326] Furthermore, we show that the material can be regenerated in aqueous phase at room temperature due to the complete reversibility of the interactions in the presence of liquid water while maintaining the MOF structure and active sites.
[0327] 7.2 Spectral characterization
[0328] The samples were pressed (10 2 MPa) to a self-supporting disk (2cm 2 The pellets were placed in a quartz home-made in-situ cell equipped with a KBr window for FTIR measurements during formaldehyde adsorption. A removable quartz sample holder allowed the pellets to be adjusted in the IR beam for spectrum acquisition and moved to the heater on top of the cell for thermal treatment. The cell was connected to a quartz in-situ cell for evacuation, calcination step (P 残留 =10 -6 -10 -9 bar) and a vacuum line for introducing formaldehyde into the infrared unit.
[0329] Gaseous formaldehyde was obtained by thermal decomposition of paraformaldehyde in a quartz reactor using a heat gun at 70 °C.
[0330] The formaldehyde was adsorbed at room temperature and the pressure was measured by a pressure gauge (10 -4 -10 -1 The pressure of formaldehyde in the FTIR cell was measured in the bar range. The spectral range was 400–5500 cm on a Nicolet Nexus spectrometer equipped with an extended KBr beam splitter and a deuterated triglycine sulfate detector (DTGS). -1 Within the range of 4cm -1 Transmission FTIR spectra were recorded after the introduction of formaldehyde at 1000 nm resolution and 64 scans.
[0331] 7.3 Results and Discussion
[0332] a) Interaction between formaldehyde and Al-3.5-PDA during adsorption
[0333] The complete FTIR spectrum of Al-3.5-PDA shows a peak at 3699-3691 cm -1 The two bands at , which correspond to the inorganic infinite chain μ 2 -OH stretching mode of hydroxyl group at 3424 cm -1The NH stretching mode of the pyrazole linker is present at 3153 cm -1 This is consistent with theoretical and experimental studies of pyrazole derivatives.
[0334] Formaldehyde adsorption was performed on Al-3.5-PDA at room temperature by delivering small doses of formaldehyde. The FTIR spectra recorded after each dose are shown in Figure 12.
[0335] By considering the main bands formed, it is possible to characterize the transformation of formaldehyde upon adsorption, which leads to the formation of primary alcohols.
[0336] It is characterized by a band at 1076 cm -1 The 1298 cm -1 The bands at are assigned to the OH deformation mode and CH 2 Swing [Fig. 12.c)]. 1216cm -1 The bands at 1139 cm-1 are assigned to OH bending in plane vibrations, and the -1 The bands at are assigned to CH shaking [Fig. 12.c) and Fig. 12.d)]. These bands are characteristic of primary alcohols formed upon chemisorption of formaldehyde and subsequent opening of its C=O double bond. This clearly demonstrates the interaction between the internal pores of Al-3.5-PDA and the carbon of formaldehyde through the creation of covalent bonds.
[0337] In addition, the adsorbed formaldehyde binds to the μ of Al-3.5-PDA through hydrogen bonds. 2 -OH hydroxyl groups interact. This is reflected by the -1 The band at 3673cm -1 There are isosbestic points at 3640 and 3480 cm -1 A new complex broad band (which corresponds to a typical hydrogen OH-O bond) appears between the two bonds [Figure 12a) and Figure 12e)].
[0338] The second hydrogen-bonded compound formed between the formaldehyde and the NH group of the pyrazole carboxylic acid linker, which is mainly shown as [Figure 12.b) 12.e)], at 3425, 3417 and 3336 cm -1 The band at 3301cm -1 The isosbestic points appear at 3289 and 3034 cm -1 A complex broad band appears between the two, which corresponds to the formation of N--HO hydrogen bonds through the lone oxygen pair from formaldehyde (3226 and 3153 cm -1 ).
[0339] 3031-2965cm -1 The band at [Fig. 12.b)] can be assigned to the -CH mode of chemisorbed formaldehyde (ie to the methanol groups thus formed).
[0340] Without wishing to be bound by any particular theory, it is believed that the reaction between the pyrazole linker and the formaldehyde occurs via the lone pair of imine nitrogens, reacting and forming a covalent bond on the carbon of the formaldehyde, followed by loss of a proton from the other nitrogen to form pyrazol-1-yl-methanol (also known as 1-oxymethylpyrazole). The oxymethyl group so formed is bonded to the inorganic infinite chain μ from the framework by the OH group from the formed oxymethyl group. 2 -OH Hydrogen bonding between the oxygens of the hydroxyl group and through hydrogen bonding from the oxymethyl group Fig.13 a)] and the remaining nitrogen from the pyrazolidine linker [ Fig.13 b)] is stabilized by hydrogen bonding between OH-N.
[0341] b) Interaction between formaldehyde and DUT-67(Zr)-PZDC during adsorption
[0342] It has been observed that these interactions are not limited to Al-3.5-PDA. In fact, the same kind of interactions occur with a porous Zr pyrazole carboxylate MOF denoted DUT-67(Zr)-PZDC (prepared with the same linker as Al-3.5-PDA (i.e., 3.5 pyrazole dicarboxylic acid) upon formaldehyde adsorption.
[0343] Formation of oxymethyl groups Fig.14 b) and c)] by bands at 1131, 1076, 1280 and 1202 cm -1 The bands are indicated as (i) CH shaking; (ii) ν(CO) mode; (iii) OH deformation mode and CH 2 Rocking; (vi) OH bending in plane vibration and mainly showing, [ Fig.14 The stabilization of the formed oxymethyl groups on the -OH / -NH groups is shown by: -1 The -OH at the Brunnenstein acid site and at 3463 cm -1 The characteristic bands of the basic group -NH at the -1 and broad bands at 3523 and 3336 cm -1 Formed at.
[0344] c) Regeneration of AI-3.5-PDA in aqueous solution at room temperature
[0345] Regeneration of the material after formaldehyde adsorption was achieved by placing 20 mg of Al-3.5-PDA pellets after saturation with deuterated formaldehyde in a beaker, slowly filling with 100 mL of distilled water and leaving at room temperature for 3 h. Finally, the material was replaced in the FTIR unit and placed under secondary vacuum to remove residual water. Fig.15 FTIR spectra obtained at various steps during regeneration, specifically after cumulative quenching and rinsing of the sample in 100 mL of water at room temperature are shown. 2 When the -OH and NH groups are completely regenerated, there is no chemically adsorbed deuterated formaldehyde v(CD) (2300-2050 cm -1 Characteristic diagram of the pores.
[0346] This indicates that the material was successfully regenerated in the aqueous phase at room temperature. The chemical adsorption of formaldehyde was reversible and the material was fully regenerated at room temperature.
[0347] Applying mechanical washing in water or specific solvents can fully or partially regenerate the material after adsorption of pollutants at room temperature, even if the main interaction occurs via covalent bonds.
[0348] Even after adsorption of some gaseous toluene (at an equilibrium pressure of 8 mbar), the material can be regenerated. Figure 16-Figure 17 As shown, the characteristic pattern of adsorbed toluene (at 3025 and 2917 cm -1 The v(CH)) at 400 nm completely disappeared, indicating successful regeneration at room temperature.
[0349] d) Formaldehyde and UiO-66(Zr)-NH 2 Interactions between (comparative examples provided for reference purposes only)
[0350] During some activation steps, UiO-66(Zr)-NH 2 The FTIR spectrum can be found in Fig.18 ), of which 5250cm -1 The weak band at is the molecular H 2 O(v+δ(OH)) characteristic. 3671cm -1 The band at 3 -OH ν(OH) stretching mode of hydroxyl group. 3500-3393cm -1 The band at corresponds to the ν as (NH 2 ) and v s (NH 2 ) Extension frequency: 3100-2800cm -1The bands at 1497 and 1622 cm correspond to some CH modes; the v(COO-) stretching frequencies of structural carboxylic acids are characteristic at 1497 and 1622 cm -1 Visible at 1337 and 1258cm -1 The band at is attributed to the v(CN) mode.
[0351] In UiO-66(Zr)-NH 2 The FTIR spectrum obtained after formaldehyde adsorption on the sample shows Fig.19 During the adsorption of formaldehyde, the -1 The band at is due to the presence of an amino linker in the structure as (NH) and v s The (NH) pattern gradually decreases, indicating that the amino group is bonded to the formaldehyde either by covalent bonding (as suggested in the literature) or by hydrogen bonding. -1 (carbonyl stretching frequency) A feature appears in the range with v(C=O) positions from gaseous formaldehyde, indicating that some formaldehyde may be physically adsorbed or weakly H-bonded. Some features at 1724 and 1683 cm -1 The interpretation of these bands is difficult and ambiguous due to their complex nature (and primarily because of their positive / negative nature). The positive / negative shape of these bands suggests that they may be due to some minor structural changes. -1 The band at 1620 cm-1 is in the stretching frequency range of carbonyl compounds and is probably due to some formaldehyde molecular interaction via lone pair electrons. Formaldehyde chemisorbed via coordination bonds on Lewis acid sites is characterized by a band at about 1620 cm-1. -1 The stretching vibrations at 1683 cm-1 correspond to the CH stretching vibrations at 2870 and 2770 cm-1 (similar to gaseous formaldehyde) (6). -1 The band observed at 4+ Some v(C=O) stretching frequencies of formaldehyde adsorbed on Lewis acid sites may be due to some structural changes.
[0352] At 1103, 1000 and 942 cm -1 Some strong features can be seen at 1110 cm-1. This indicates the presence of some poly(formaldehyde) species in the pores, indicating that formaldehyde polymerizes within the pores upon formaldehyde adsorption. This is mainly shown during thermal activation when the difference between the FTIR spectrum at 50 °C and the FTIR spectrum taken after saturation reveals a deviation of the poly(formaldehyde) species, characterized by a peak at 1110 cm-1. -1 Some strong bands at about 927 cm -1 The superposition band at Fig. 20 ).
[0353] Thermal regeneration of UiO-66-NH 2 The FTIR spectrum obtained at Fig.19 .c); Interestingly, it can be seen that 3502-3388cm -1 The band shape at did not return to its original state (black dashed spectrum acquired before formaldehyde adsorption), indicating that the amino groups of the material were not completely regenerated after heat treatment at 250°C.
[0354] These results suggest that amino-aromatic MOF materials (i.e., MOFs with NH 2 MOF materials with aromatic ligands such as UiO-66-NH 2 and MIL-125(Ti)-NH 2 is a less preferred variant of the present disclosure, as long as the adsorption of formaldehyde by these materials leads to the formation of unstable substances (polyoxymethylene) which tend to be released again at room temperature.
[0355] e) Comparative analysis: Formaldehyde release in the presence of water.
[0356] As described in the previous protocol, Al-3.5-PDA, UiO-66-NH 2 and some commercially available modified activated carbons (purchased from ) for comparative analysis of formaldehyde desorption. The desorption curve is shown in Fig. 22 The results show that pyrazole-based MOFs retain FA more effectively at elevated temperatures, especially in the presence of humidity. No formaldehyde is released when evacuated under a wet stream close to room temperature [23°C-35°C]. On the other hand, amino-based MOFs release some formaldehyde starting from room temperature due to the formation of some unstable species as discussed previously.
[0357] f) Thermal regeneration.
[0358] The thermal regeneration of the material was investigated as follows: (i) the material was saturated with gaseous formaldehyde at an equilibrium pressure of 0.1 mbar, (ii) the material was placed under a dynamic vacuum at a temperature of 80°C for 48 h, (iii) the temperature was increased to 110°C and the material was placed for 4 h. The FTIR spectra acquired after each step are presented in Fig.23 middle.
[0359] Based on the characteristic bands of the formed oxymethyl groups (at 30112965 cm -1 From the integration of v(CH) at 10 °C, it can be inferred that thermal regeneration at 80 °C resulted in 90% formaldehyde desorption and that at 110 °C the material was fully regenerated.
[0360] This confirms that Al-3.5-PDA is fully regenerated between 75 °C and 110 °C.
[0361] g) Formaldehyde in imidazole / Al 2 O 3 Adsorption on
[0362] In with Al 2 O 3 The FTIR spectrum obtained after adsorption of formaldehyde on the mixed imidazole (1 / 10 mass ratio) is shown in Fig.24 In. 1324cm -1 The bands at (ν(NC)) gradually decrease and at 1541 and 1575 cm -1 The band at 1700 cm-1 gradually decreases (in-plane bending mode of imidazole); -1 There are no strong bands visible nearby, all of which indicate that there is a change in the v(C=O) of formaldehyde upon adsorption on imidazole, which involves a chemical reaction. In addition, similar to the adsorption of formaldehyde on the pyrazole linker, there are strong bands at 1281 and 1221 cm -1 Some features appear at the 2 The rocking as well as the OH bending indicate that the adsorption pattern of formaldehyde with imidazole is similar to that with pyrazole.
[0363] This suggests that imidazole groups with accessible pyridinic and pyrrolic nitrogens can be used for the purposes of this application (once combined with a carboxylic acid to build a MOF, but remaining fully accessible to interact with an aldehyde).
[0364] h)CO 2 Co-adsorption of water
[0365] In order to verify the CO 2 Whether the presence of CO may affect the absorption of other pollutants, a high concentration (about 3000 ppm, thus greatly exceeding the normal air concentration (400 ppm)) of CO was carried out in the presence of 50% relative humidity. 2 Figure 25 shows the adsorption of water and CO 2 The breakthrough curve in the case of co-absorption, Fig.26 The maximum CO in the presence of 50% relative humidity is summarized 2 Absorption capacity.
[0366] Amino-functionalized MOFs exhibit low or no CO in the presence of 50% relative humidity 2 The reason may be the interaction of water with CO through hydrogen bonding. 2 The opposite is possible for physical adsorption.
[0367] Al-3.5-PDA with accessible -NNH- groups exhibits negligible CO 2 Adsorption capacity. 2 In contrast, the affinity of water in the presence of 50% RH is significantly higher; the reason may be that in the case of amino-functionalized MOFs, compared with CO 2 Compared with simple physical adsorption in the case of CO, the interaction occurs through hydrogen bonding with water. MIL-140A, MIL-140B, and ZIF-8 hydrophobic MOFs exhibit relatively low adsorption capacities with spontaneous CO 2 leakage, which also indicates that the 2 It has a higher affinity for water.
[0368] Basolite F-300 / Fe-BTC showed the best maximum adsorption of CO 2 The amount, however the shape of the breakthrough curve does not exhibit a no leakage region and is rather flat, indicating an unfavorable or linear isotherm, or kinetic limitation in the presence of 50% relative humidity.
[0369] Some studies have focused on describing the relationship between water and CO 2 Adsorption on various adsorbents. Binary CO obtained in the literature 2 - The water adsorption data show very different behavior; for the dilute system, the presence of a small amount of water improves the CO adsorption at low partial pressures. 2 adsorption, but at higher CO 2 and water concentrations, water has been shown to inhibit CO 2 The second case is consistent with our experimental results.
[0370] Therefore, the above analysis proves that in the case of MOFs suitable for this application, CO 2 The presence of does not affect the adsorption / filtration of target VOCs such as formaldehyde. This is in stark contrast to conventional amine-grafted porous solids, which have been shown to absorb and remove ions from air as well as CO 2 formaldehyde is well captured in the 2 There is a strong competition between NH4+ and formaldehyde adsorption.
[0371] i)CO 2 Co-adsorption of formaldehyde on Al-3.5-PDA
[0372] CO was carried out as follows 2 Co-adsorption of formaldehyde and Al-3.5-PDA samples: (i) using gaseous CO at an equilibrium pressure of 5 mbar. 2saturating the material, (ii) gradually feeding formaldehyde into the in-situ unit [ Fig. 27 a) b)], (iii) after reaching formaldehyde saturation (complete consumption of Brønsted acid sites), placing the in-situ unit under vacuum to remove the gas phase, and (iv) finally sanding down some of the gaseous CO at an equilibrium pressure of 5 mbar 2 .
[0373] In brief, based on the spectral data [ Fig. 27 ], the chemical adsorption of formaldehyde causes the physical adsorption of CO 2 Desorption (see at 2340 cm -1 ν as (CO 2 ) band reduction[ Fig. 27 b)], accompanied by a gradual increase in all characteristic bands of oxymethyl groups Fig. 27 a)). Will CO 2 Delivery to a material saturated with formaldehyde affects neither the shape nor the intensity of the characteristic bands of chemisorbed formaldehyde, indicating the absence of formaldehyde desorption [ Fig. 27 c)d)e)].
[0374] j) Determination of the desorption energy in the case of Al-3.5-PDA / formaldehyde.
[0375] The desorption energy can be estimated using the Redhead method
[42] ,
[43] ).
[0376] Several flash desorptions were performed with a linear change in the +a temperature consistent with a 1st order desorption (when the adsorption / desorption is not dissociative).
[0377] Using the Polanyi-Wigner expression (1) and the kinetic expression for the desorption rate Rd given by equation (2), the desorption rate can be expressed as a function of temperature (4) taking into account the linear heating of the sample with the temperature dependence equation (3). Thus, the linear heating of the sample results in a temperature T m , at which temperature the desorption rate allows a maximum value, and the first-order derivative of expression (4) is invalid (5). Substituting expression (2) into the derivative of equation (5), after simplified rearrangement and linearization, expression (6) is obtained.
[0378]
[0379] Where R d , desorption rate; N, the amount (or concentration) of adsorbed substances; Ed, desorption energy; A, pre-exponential factor; k d , desorption kinetic constant; x, kinetic order (if non-dissociative adsorption / desorption, x = 1); T, temperature; T 0, initial temperature; R, gas constant; β, heating rate (K / min).
[0380] Therefore, through draw The function of may estimate the desorption energy ( Fig.29 )
[0381] Using this method, the desorption energy of formaldehyde from Al-3.5-PDA was estimated to be about 85.9 kJ / mol. This value is consistent with the formaldehyde retention rate shown by Al-3.5-PDA.
[0382] in conclusion
[0383] As illustrated by the previous examples, we have successfully produced a porous material (generally based on a metal-organic framework) capable of effectively capturing volatile organic products (with or without moisture) present in the air in a confined space (rooms in a residence, studios, offices, workshops, passenger compartments of vehicles, etc.), which is formed and arranged inside an air filtration device. More specifically, a specific selection of hybrid organic / inorganic crystalline materials (MOFs) has been determined, which have a high affinity for indoor air pollutants such as formaldehyde, capable of selectively and effectively retaining these pollutants between 20°C and 50°C during dry or humid air filtration, without allowing the retained target molecules to leak out during operation or static phases.
[0384] The device will be easily recycled by washing in water and will last for a large number of cycles. It will not produce harmful degradation compounds.
[0385] It has been further demonstrated that the interaction between formaldehyde and Al-3.5-PDA occurs via the creation of a covalent bond between the lone pair of electrons from the "pyridinic" nitrogen of the pyrazole(dicarboxylic acid) linker and the carbon from formaldehyde, leading to a covalent bond via the remaining nitrogen and / or with the carbon from μ 2 The oxygen of the -OH hydroxyl group undergoes hydrogen bonding to stabilize the formation of the oxymethyl group. These interaction patterns are stable even in the presence of ambient humidity, which is a key point to avoid formaldehyde release under normal conditions when the material is saturated.
[0386] We further demonstrated that room temperature water quenching was sufficient to completely regenerate Al-3.5-PDA after formaldehyde saturation, and its adsorption performance remained almost unchanged after several cycles.
[0387] Finally, these results demonstrate that metal-organic-frameworks exhibiting accessible pyrazole-N-NH groups and brynaster sites (this includes pyrazoles and imidazoles as we have shown) are promising and sustainable materials for the removal of formaldehyde from indoor air, leading to reusable filter media.
[0388] The present invention can:
[0389] - Increased capture and storage capacity of typical indoor air pollutants such as formaldehyde and more generally VOCs
[0390] - Utilizes leak-free storage to more effectively filter and retain these air pollutants (this allows for purification of air quality via a single passage through the filter media)
[0391] -Reuse the filter media multiple times through a simple and economical regeneration process set by the user
[0392] - Prevents the generation of additional pollutants
[0393] In recent years, the field of air quality has received more attention due to the high levels of pollution in large cities. As mentioned before, air pollution has a significant impact on the health of the population, such as increasing the risk of stroke, cardiovascular disease, and most importantly, increasing the risk of respiratory diseases. It is undeniable that air quality is a major health issue in the twenty-first century.
[0394] The present invention provides a new solution to this problem. As described throughout this article and shown in the examples, a selection of porous MOF materials have been identified that are more effective (adsorption capacity, stability and regeneration) in removing formaldehyde than commercial absorbents on the market. Prototype filter media with the best performing identified MOFs have been built and their efficiency has been tested and verified under real conditions ("full-scale experiments").
[0395] In summary, the present invention provides an effective tool for improving indoor air quality.
[0396] References
[0397] [1] "Depollution product for trapping volatile organic compounds, particularly formaldehyde, and method for the production thereof," August 2016.
[0398] [2] “Purificateur d’air: maison, voiture, poussiere & cigarette - Blooow.” [Online]. Available: https: / / www.blooow.com / le-fonctionnement / . [Accessed: 1 May 2019].
[0399] [3]Ashrae Fundamentals Handbook, SI Edition, 2001, page 24.5
[0400] [4]Rouquérol, F.; Rouquérol, J.; Sing, K. Adsorption by powders and porous solids; Academic Press: San Diego, 1999.
[0401] [5]L Sarkisov and A. Harrison, Mol. Simul., 2011, 37, 1248 - 1257.
[0402] [6]WO 2019 / 053048
[0403] [7]Permyakova, A.; Wang, S.; Courbon, E.; Nouar, F.; Heymans, N.; D’Ans, P.; Barrier, N.; Billemont, P.; De Weireld, G.; Steunou, N.; Frère, M.; Serre, C. Design of salt - metal organic framework composites for seasonal heat storage applications. J. Mater. Chem. A, 5, 12889 - 12898, 2017a.
[0404] [8]Cadiau, A.; Lee, J.S.; Damasceno Borges, D.; Fabry, P.; Devic, T.; Wharmby, M.T.; Martineau, C.; Foucher, D.; Taulelle, F.; Jun, C.-H.; Hwang, Y.K.; Stock, N.; De Lange, M.F.; Kapteijn, F.; Gascon, J.; Maurin, G.; Chang, J.-S.; Serre, C. Design of Hydrophilic Metal Organic Framework Water Adsorbents for Heat Reallocation. Adv. Mater., 27, 4775 - 4780, 2015.
[0405] [9]Permyakova, A.; Skrylnyk, O.; Courbon, E.; Affram, M.; Wang, S.; Lee, U.-H.; Valekar, A.H.; Nouar, F.; Mouchaham, G.; Devic, T.; De Weireld, G.; Chang, J.-S.; Steunou, N.; Frère, M.; Serre, C. Synthesis Optimization, Shaping, and Heat Reallocation Evaluation of the Hydrophilic Metal-Organic Framework MIL-160(Al). Chem. Sus. Chem., 10, 1419 - 1426, 2017b.
[0406]
[10] WO2009 / 123484
[0407]
[11] M. Rose et al. Adv. Eng. Mater. 2011, 13, 356 - 360.
[0408]
[12] R. Ostermann et al. Chem. Commun. 2011, 47, 442 - 444.
[0409]
[13] J. Ren et al. Int. J. Hydrogen Energy 2015, 40, 9382 - 9387.
[0410]
[14] M. R. Khan et al. J. Mater. Eng. Perform. 2016, 25, 1276 - 1283.
[0411]
[15] WO 2009 / 07767
[0412]
[16] US 2014 / 0213832
[0413]
[17] Kim, P.-J.; You, Y.-W.; Park, H.; Chang, J.-S.; Bae, Y.-S.; Lee, C.-H.; Suh, J.-K. Separation of SF6 from SF6 / N-2 mixture using metal-organic framework MIL-100(Fe) granule Chem. Eng. J. 262, 683 - 690, 2015.
[0414]
[18] Farhad Fathieh et al., Sci. Adv. 2018;4:eaat3198, pp. 1–9.
[0415]
[19] . G. Férey et al. Science 2005, 309, 2040-2042.
[0416]
[20] YKHwang et al. Angew.Chem.Int.Ed.Engl.2008, 47, 4144-4148.
[0417]
[21] A. Demessence et al., Adsorption properties in high optical quality nanoZIF-8 thin films with tunable thickness, J. Mater. Chem., 2010, 20, 7676-7681.
[0418]
[22] C. Gomes Silva et al. Chem. Eur. J. 2010, 16, 11133-11138.
[0419]
[23] MABanares and IEWachs, J.Raman Spectrosc., 2002, 33, 359-380; T. Lesage, C. Verrier, P. Bazin, J. Saussey, M. Daturi, Phys.Chem.Chem.Phys.5 (2003) 4435-4440.; S. Thomas, O. Marie, P. Bazin, L. Lietti, CG Visconti, M. Corbetta, F. Manenti and M. Daturi, Catal. Today, 2017, 283, 176-184.
[0420]
[24] Thommes et al., IUPAC Technical Report, Pure Appl. Chem., 2015, 87(9-10), 1051-1069.
[0421]
[25] KY Cho et al., “Synthesis of amine-functionalized ZIF-8 with 3-amino-1, 2, 4-triazole by postsynthetic modification for efficient CO2-selective adsorbents and beyond,” J. Mater. Chem. A, Vol. 6, No. 39, pp. 18912-18919, 2018
[0422]
[26] H. Reinsch et al., “Structures, sorption characteristics, and nonlinear optical properties of a new series of highly stable aluminum MOFs,” Chem. Mater., vol. 25, no. 1, pp. 17–26, 2013.
[0423]
[27] Y. Fu et al., “Anamine-functionalized titanium metal-organic framework photocatalyst with visible-light-induced activity for CO2 reduction,” Angew. Chemie-Int. Ed., Vol. 51, No. 14, pp. 3364-3367, 2012;
[0424]
[28] S.-N. Kim, J. Kim, H.-Y. Kim, H.-Y. Cho, and W.-S. Ahm, “Adsorption / catalytic properties of MIL-125 and NH2-MIL-125,” Catal. Today, vol. 204, pp. 85–93, April 2013.
[0425]
[29] S.Bemt, V.Guillerm, C.Serre, and N.Stock, “Direct covalent post-synthetic chemical modification of Cr-MIL-101 using nitrating acid,” Chem. Commun., Vol. 47, No. 10, pp. 2838-2840, 2011.
[0426]
[30] J. Jacobsen, H. Reinsch, and N. Stock, “Systematic Investigations of the Transition between Framework Topologies in Ce / Zr-MOFs,” Inorg. Chem., Vol. 57, No. 20, pp. 12820 - 12826, 2018.
[0427]
[31] C. Wang, X. Lui, N. Keser Demir, J. P. Chen, and K. Li, “Applications of Water Stable Metal-Organic Frameworks,” Chem. Soc. Rev., Vol. 45, No. 18, pp. 5107 - 5134, 2016.
[0428]
[32] D. De Recherches, R. D. D. Scientifiques, and D. De Recherches, “‘UNIVERSITE VERSAILLES SAINT-QUENTIN’ ECOLE DOCTORALE N°571 Sciences chimiques: molécules, matériaux, instrumentation et biosystèmes Chimie Par Mr Paul Rouschmeyer Nouveaux solides hybrides poreux luminescernts à base de tétrazine,” 2015.
[0429]
[33] E. Alvarez, “Traitement de l’air par des matériaux hybrides de type Metal Organic Frameworks,” p. 230, 2016.
[0430]
[34] S. Patra et al., “Design of metal organic framework-enzyme based bioelectrodes as a novel and highly sensitive biosensing platform,” J. Mater. Chem. B, Vol. 3, No. 46, pp. 8983 - 8992, November 2015.
[0431]
[35] S. Biswas et al., “Enhanced selectivity of CO2 over CH4 insulphonate-, carboxylate- and iodo-functionalized UiO-66 frameworks,” Dalt. Trans., vol. 42, no. 13, p. 4730, March 2013.
[0432]
[36] B. Van de Voorde et al., “Isolation of Renewable Phenolics by Adsorption on Ultrastable Hydrophobic MIL-140 Metal-Organic Frameworks,” ChemSus Chem, vol. 8, no. 18, pp. 3159–3166, September 2015.
[0433]
[37] E. Plessers et al., “Zr-Based MOF-808 as Meerwein-Ponndorf-Verley Reduction Catalyst for Challenging Carbonyl Compounds,” Catalysts, vol. 6, no. 7, p. 104, July 2016.
[0434]
[38] A. Permyakova et al., “Design of salt-metal organic framework composites for seasonal heat storage applications,” J. Mater. Chem. A, vol. 5, no. 25, pp. 12889–12898, June 2017.
[0435]
[39] Dedecker, K. et al. Metal-Organic Frameworks for Cultural Heritage Preservation: The Case of Acetic Acid Removal. ACSAppl.Mater.Interfaces 10, 13886-13894 (2018).
[0436]
[40] Cadiau,Amandine,Lee,Ji Sun,Borges,Daiane Damasceno,Special, “Designof Hydrophilic Metal Organic Framework Water Adsorbents for HeatReallocaton”,ADVANCED MATERIALS 2015, October 27, October 32, 4775-4780.
[0437]
[41] Y.-R.Lee,M.-S.Jang,H.-Y.Cho,H.-J.Kwon,S.Kim,and W.-S.Ahn,“ZIF-8:A Comparison of Synthesis methods,” Chem.Eng.J., No. 271, No. 276-280, July 2015.
[0438]
[42] Redhead PA.Thermal desorption of gases.Vacuum.1962:12(5):2
[0439]
[43] Webb PA.Introduction to Chemical Adsorption Analytical Techniquesand Their Applications to Catalysis.MIC Tech Publ.2003:13(January):1-4.
Claims
1. Use of a porous water-stable metal-organic framework (MOF) material for selectively adsorbing aldehyde volatile organic compounds (VOCs) rather than non-aldehyde VOCs from a gas environment, wherein the MOF material comprises < an average pore size of the MOF material and a hydrophilic core formed by a basic group and an oxygen-containing species that accepts or donates hydrogen bonds in the MOF material, wherein the basic group is covalently bonded to the MOF material but not to the metal site of the MOF material, wherein the ligand in the MOF material is an N-containing heterocyclic ligand having at least one of the available basic groups embedded in the ligand itself, the basic group not participating in the bonding with the metal site of the MOF material and wherein the crystal structure of the MOF material measured by X-ray diffraction pattern or IR spectroscopy and the average pore size calculated by a nitrogen adsorption / desorption isotherm method at -196°C at 105 Pa remain unchanged within experimental error after exposure to a gas environment with 50% relative humidity (RH) at 100°C and atmospheric pressure for 24 hours, or after being treated in water at 100°C for 12 hours.
2. Use of a porous water-stable metal-organic framework material according to claim 1, wherein the MOF material is alone or mixed with other MOFs, zeolites and / or activated carbon.
3. Use of the porous water-stable metal-organic framework material according to claim 1 or 2, wherein the MOF material is contained in a filter medium for air purification.
4. The use of the porous water-stable metal-organic framework material according to claim 3, wherein when the polluted air is ≤60000h -1 The filter medium is leak-free for aldehyde volatile organic compounds when an air velocity of 100° C. flows through the filter medium, and the filter medium retains 100% of the aldehydes at atmospheric pressure and at an operating temperature in the range of 10° C. to 50° C.
5. Use of a porous water-stable metal-organic framework material according to claim 1, wherein the metal atoms of the MOF material are selected from trivalent or tetravalent metals from Sc, Y, Tb, Gd, Ce, Ln, La, Ti, Zr, Fe, Al or Cr.
6. Use of a porous water-stable metal-organic framework material according to claim 1, wherein the N-heterocyclic ligand is present in the MOF material in the form of an N-heterocyclic polycarboxylic acid ligand.
7. Use of a porous water-stable metal-organic framework material according to claim 1, wherein the oxygen-containing species that accepts or donates hydrogen bonds in the MOF material exists in the form of oxygen-clusters, oxygen-hydroxyl clusters and / or OH.
8. Use of a porous water-stable metal-organic framework material according to claim 1, wherein the MOF material has a crystal structure selected from the following: UiO-66, MIL-53, MIL-68, MIL-125, MIL-101, CAU-10, MIL-160, PDA-type MOF materials.
9. Use of a porous water-stable metal-organic framework material according to claim 1, wherein the MOF material is selected from Al-3,5-PDA ("MOF-303"), DUT-67(Zr)-PZDC, CAU-10(Al)-pyridine, CAU-10(Al)-pyrazine or a mixture of two or more thereof.
10. Use of the porous water-stable metal-organic framework material according to claim 3, wherein the filter medium is included in a system for air purification.
11. A method for purifying air by selectively adsorbing aldehyde volatile organic compounds from air rather than non-aldehyde VOCs, the method comprising contacting the air to be purified with a porous water-stable MOF material, wherein the MOF material comprises < an average pore size of the MOF material and a hydrophilic core formed by a basic group and an oxygen-containing species that accepts or donates hydrogen bonds in the MOF material, wherein the basic group is covalently bonded to the MOF material but not to the metal site of the MOF material, wherein the ligand in the MOF material is an N-containing heterocyclic ligand having at least one of the available basic groups embedded in the ligand itself, the basic group not participating in the bonding with the metal site of the MOF material and wherein the crystal structure of the MOF material measured by X-ray diffraction pattern or IR spectroscopy and the average pore size calculated by a nitrogen adsorption / desorption isotherm method at -196°C at 105 Pa remain unchanged within experimental error after exposure to a gas environment with 50% relative humidity (RH) at 100°C and atmospheric pressure for 24 hours, or after being treated in water at 100°C for 12 hours.
12. The method of claim 11, wherein the MOF material is contained in a filter medium that can be regenerated to ≥75% of its adsorption / filtration capacity by heating the filter medium to a temperature ≥70°C followed by low temperature thermal desorption of the filter medium, wherein the method comprises at least one regeneration cycle.
13. The method of claim 11, wherein the MOF material is contained in a filter medium that can be regenerated to ≥ 75% of its adsorption / filtration capacity by washing with water and / or hydroalcoholic solutions at room temperature, wherein the method comprises at least one regeneration cycle.
14. The method according to claim 11, wherein the MOF material has been coated on a carrier in the form of a plate, a honeycomb carrier, a grid, or any shape used in air purification filter media, or on a carrier having a filtering capacity.
15. The method of claim 14, wherein the MOF material is in the form of a shaped body.
16. The method according to claim 15, wherein the MOF material is made into a shaped body using a binder, a lubricant or other additives commonly used in the preparation of adsorbent shaped bodies.
17. The method of claim 15 or 16, wherein the shaped MOF material is contained in the cavity of a hollow support.
18. The method of claim 14, further comprising the step of soaking the MOF material in water and / or a hydroalcoholic solution at room temperature for a suitable amount of time.
19. The method of claim 14, wherein the air is room air.
Citation Information
Patent Citations
Compressed chewing gum comprising an encapsulation delivery system comprising natural resin
WO2009007767A1
Adsorbents comprising organic-inorganic hybrid nanoporous materials for sorption of water or alcohol and use thereof
WO2016186454A1
Metal organic frameworks for the capture of volatil organic compounds
WO2019053048A1
Metal-organic framework material for methane adsorption separation and preparation method thereof
CN102962037A
UiO-66 based MOF (metal organic framework) material for indoor formaldehyde purification at room temperature and application of material
CN110038517A